Pressure sensitive adhesive sheet

A water-based adhesive composition with a rubber latex adhesive layer and oxazoline-containing undercoat enhances adhesion to resin films, addressing glue residue issues and environmental concerns by improving anchoring and peeling efficiency.

JP2025014435APending Publication Date: 2025-01-30NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023116983
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Existing adhesive compositions containing rubber latex face challenges in anchoring to polyolefin resin films, leading to potential glue residue and difficulty in peeling without damaging the substrate, especially when using water-based adhesives to reduce organic solvent use.

Method used

A water-based adhesive composition with a rubber latex adhesive layer and an undercoat layer containing a water-soluble polymer with oxazoline groups is used, enhancing anchoring to resin films without relying on organic solvents, thereby improving adhesion and reducing glue residue.

Benefits of technology

The solution provides a robust adhesive layer that securely adheres to resin films, minimizing glue residue and facilitating easy peeling, while reducing environmental impact by minimizing organic solvent use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014435000001_ABST
    Figure 2025014435000001_ABST
Patent Text Reader

Abstract

To provide a pressure sensitive adhesive sheet having a resin film base material with excellent anchorability of an adhesive layer, without relying on an organic solvent.SOLUTION: A pressure sensitive adhesive sheet includes a resin film base material, an undercoat layer and an adhesive layer in this order. The undercoat layer is disposed at least on one side of the resin film base material in contact with the adhesive layer. The adhesive layer is composed of an adhesive composition including rubber-based latex and an aqueous cross-linking agent. The aqueous cross-linking agent includes an aqueous cross-linking agent including at least one functional group selected from an oxazoline group, an isocyanate group and an epoxy group. The undercoat layer includes water dispersion type polymer having an oxazoline group.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive sheet. [Background technology]

[0002] Generally, adhesives (also called pressure-sensitive adhesives; the same applies below) are in a soft solid (viscoelastic) state at temperatures around room temperature and have the property of easily adhering to an adherend when pressure is applied. Taking advantage of such properties, adhesives are widely used in various fields for purposes such as bonding, fixing, surface protection, masking, and marking, for example in the form of an adhesive sheet having an adhesive layer on a substrate. Patent Document 1 is an example of a document disclosing this type of prior art. Patent Document 1 describes an adhesive sheet having an adhesive layer formed on one side of a polyvinyl chloride film from an aqueous adhesive composition containing rubber latex.

[0003] As a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer on a substrate, one having an undercoat layer on the substrate is used. By providing an undercoat layer, the anchoring property of the pressure-sensitive adhesive layer to the substrate is improved, and when the pressure-sensitive adhesive sheet is removed from the adherend, the occurrence of a problem (adhesive residue) in which a residue of the pressure-sensitive adhesive remains on the surface of the adherend can be suppressed. Patent documents 2 and 3 are cited as technical documents disclosing such undercoat layers. Patent document 2 describes forming an undercoat layer made of an oxazoline group-containing acrylic polymer on one side of a polyethylene terephthalate film, and forming an acrylic pressure-sensitive adhesive layer thereon. Patent document 3 describes providing an undercoat layer made of a water-soluble oxazoline group-containing acrylic polymer between a polarizing film and an acrylic pressure-sensitive adhesive layer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 4676945 [Patent Document 2] JP 2011-149002 A [Patent Document 3] Patent No. 4841267 Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, from the viewpoint of environmental consideration and reduction of petroleum resources, reduction of organic solvent usage is required. From such a viewpoint, for example, for rubber-based adhesives, it is more desirable to use an aqueous adhesive composition containing rubber latex than a solvent-based adhesive composition in which the adhesive component is dissolved in an organic solvent. However, adhesives formed from rubber-based latex-containing adhesive compositions such as natural rubber latex tend to have insufficient anchoring properties to resin film substrates compared to adhesives formed from solvent-based adhesive compositions. In particular, when a polyolefin-based resin film is used as the resin film substrate, the rubber-based latex-containing adhesive composition tends to have a harder time anchoring to the polyolefin-based resin film, and there is a risk of adhesive residue being generated when the adhesive sheet is removed from the adherend. For example, an adhesive sheet used for surface protection of an adherend is usually peeled off (re-peeled off) from the adherend after being attached to the surface of the adherend and achieving the purpose of protection. If the adhesive sheet used for such purposes does not have sufficient anchoring properties to the substrate, there is a risk of adhesive residue being generated when the adhesive sheet is re-peeled off from the adherend, which is undesirable. In addition, adhesive sheets with poor anchoring properties of the adhesive layer may leave adhesive residue on the surface of the adherend when reworked (repositioned). Reworking refers to the process of peeling the adhesive sheet off the adherend and repositioning it when the adhesive sheet is misattached to the adherend or the position of the attachment point is misaligned. Furthermore, if the adhesive layer does not have good anchoring properties, the adhesive layers may come into unintentional contact with each other when using the adhesive sheet, and the adhesive layers may peel off from the substrate when trying to peel them off. In such cases, the adhesive sheet can no longer be used as a product.

[0006] As a method for improving anchoring ability, a method of modifying the substrate surface by corona discharge treatment or the like is known. However, corona discharge treatment does not provide the expected effect for rubber-based latex-containing pressure-sensitive adhesive compositions. In addition, the use of an undercoat agent containing an organic solvent runs counter to the trend toward eliminating organic solvents, which reduces the significance of adopting a rubber-based latex-containing pressure-sensitive adhesive composition.

[0007] The present invention has been made in view of the above circumstances, and has an object to provide a pressure-sensitive adhesive sheet in which an adhesive layer formed using a rubber-based latex is well anchored to a resin film substrate without relying on organic solvents. [Means for solving the problem]

[0008] According to this specification, a pressure-sensitive adhesive sheet is provided having a resin film substrate, an undercoat layer, and a pressure-sensitive adhesive layer in this order. The undercoat layer is provided on at least one surface of the resin film substrate and is in contact with the pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition containing a rubber latex and an aqueous crosslinking agent. The aqueous crosslinking agent contains an aqueous crosslinking agent having at least one functional group selected from an oxazoline group, an isocyanate group, and an epoxy group. The undercoat layer contains a water-dispersible polymer having an oxazoline group. By blending a water-based crosslinking agent having a specific functional group with a pressure-sensitive adhesive composition containing a rubber-based latex to form a pressure-sensitive adhesive layer, and using a water-dispersible polymer having an oxazoline group as an undercoat, the anchoring property of the pressure-sensitive adhesive layer to the resin film substrate can be improved. According to the above configuration, a pressure-sensitive adhesive sheet is realized in which the pressure-sensitive adhesive layer formed using a rubber-based latex is firmly anchored to the resin film without relying on organic solvents. The pressure-sensitive adhesive sheet does not substantially use organic solvents or uses a reduced amount of organic solvents, which is desirable in terms of environmental hygiene and non-petroleum resources. In this specification, "anchoring property" refers to the resistance of the adhesive layer to peeling from the substrate, regardless of whether the substrate and the adhesive layer are in direct contact with each other, in other words, the resistance to destruction (anchor destruction) between the adhesive layer and the substrate. Therefore, in this specification, the term "anchoring property of the adhesive layer to the substrate" or an equivalent expression is used even for a configuration in which an undercoat layer is present between the substrate and the adhesive layer.

[0009] In some preferred embodiments, the resin film substrate is a polyolefin-based resin film substrate. A rubber-based latex-containing pressure-sensitive adhesive composition is difficult to anchor to a resin film, particularly a polyolefin-based resin film, but according to the technology disclosed herein, the pressure-sensitive adhesive layer contains a specific aqueous crosslinking agent and uses a water-dispersible polymer having an oxazoline group as an undercoat, so that the pressure-sensitive adhesive layer can be firmly anchored to the polyolefin-based resin film substrate.

[0010] In some preferred embodiments, the glass transition temperature (Tg) of the water-dispersible polymer having an oxazoline group is not higher than 0° C. By using an oxazoline group-containing water-dispersible polymer having a low Tg as an undercoat agent, excellent anchoring properties are easily obtained.

[0011] In some preferred embodiments, the content of the aqueous crosslinking agent in the pressure-sensitive adhesive layer is 0.1 parts by weight or more based on 100 parts by weight of the rubber latex, based on the non-volatile content. The pressure-sensitive adhesive layer containing the aqueous crosslinking agent in a predetermined amount or more can adhere well to the undercoat layer containing the water-dispersible polymer having an oxazoline group, and can exhibit good anchoring properties. In addition, by containing the aqueous crosslinking agent in a predetermined amount or more, the pressure-sensitive adhesive layer has an appropriate cohesive force and is less likely to leave adhesive residue.

[0012] In some embodiments, the thickness of the undercoat layer is 0.01 μm or more and 3 μm or less. By setting the thickness of the undercoat layer within the above range, the anchoring power improvement effect due to the arrangement of the undercoat layer can be preferably exhibited.

[0013] In some embodiments, the rubber latex contains 50% or more by weight of natural rubber latex based on the non-volatile content. Natural rubber latex usually contains impurities such as proteins, making it difficult to obtain good anchoring properties for resin films such as polyolefin resin films, but according to the technology disclosed herein, by including a specific aqueous crosslinking agent in the pressure-sensitive adhesive layer and using a water-dispersible polymer having an oxazoline group as an undercoat agent, the pressure-sensitive adhesive layer formed containing the rubber latex mainly composed of natural rubber latex can be firmly anchored to the resin film substrate.

[0014] The adhesive layer of the adhesive sheet disclosed herein is well anchored to the resin film substrate, so that adhesive residue is unlikely to be left behind when peeled off from an adherend, and therefore the sheet is suitable as an adhesive sheet for surface protection that is attached to the surface of an adherend, achieves its protective purpose, and is then peeled off from the adherend. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a cross-sectional view illustrating a schematic diagram of a pressure-sensitive adhesive sheet according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] A preferred embodiment of the present invention will be described below. Matters other than those specifically mentioned in this specification that are necessary for carrying out the present invention can be understood by a person skilled in the art based on the teachings on carrying out the invention described in this specification and the common general knowledge at the time of filing. The present invention can be carried out based on the contents disclosed in this specification and the common general knowledge in the field. In addition, in the following drawings, members and parts that perform the same function may be described by using the same reference numerals, and duplicated descriptions may be omitted or simplified. In addition, the embodiments described in the drawings are schematic in order to clearly explain the present invention, and do not necessarily accurately represent the size or scale of the pressure-sensitive adhesive sheet of the present invention that is actually provided as a product.

[0017] The concept of adhesive sheet here may include those called adhesive tape, adhesive label, adhesive film, etc. The above-mentioned adhesive layer is typically formed continuously, but is not limited to such a form, and may be an adhesive layer formed in a regular or random pattern such as a dotted or striped pattern. The adhesive sheet disclosed herein may be in the form of a roll or a sheet. Alternatively, it may be cut or punched into an appropriate shape depending on the application or mode of use.

[0018] In addition, in this specification, the term "adhesive" refers to a material that exhibits a soft solid (viscoelastic) state in a temperature range around room temperature and has the property of easily adhering to an adherend by pressure, as described above. The adhesive referred to here is generally a material having a complex tensile modulus E * (1Hz)<10 7 dyne / cm 2 The material may be a material having the properties satisfying the above (typically, a material having the above properties at 25°C).

[0019] <Adhesive sheet configuration example> The adhesive sheet disclosed herein is an adhesive sheet with a resin film substrate having an adhesive layer on one or both sides of the resin film substrate (support), and has a resin film substrate, an undercoat layer, and an adhesive layer in this order. The undercoat layer is provided on at least one side of the resin film substrate and is in contact with the adhesive layer.

[0020] The structure of an adhesive sheet according to one embodiment is shown in FIG. 1. The adhesive sheet 1 includes a resin film substrate 10, an undercoat layer 30 provided on a first surface 10A of the resin film substrate 10, and an adhesive layer 20 disposed on the surface 30A of the undercoat layer 30, and is used by attaching the adhesive layer 20 to an adherend. The adhesive sheet 1 includes the resin film substrate 10, the undercoat layer 30, and the adhesive layer 20 in this order, and the undercoat layer 30 is disposed between the resin film substrate 10 and the adhesive layer 2. In the adhesive sheet 1, the other surface (back surface, second surface) 10B of the resin film substrate 10 is a surface having releasability (release surface). The adhesive sheet 1 before use (i.e., before attachment to an adherend) may be in the form of a roll 50 in which the surface (adhesive surface) 20A of the adhesive layer 20 is wound around a core (roll core) 52 in a roll shape so as to abut against the back surface 10B of the resin film substrate 10, as shown in FIG. 1, thereby protecting the surface 20A. It may also be in the form of a roll without a core 52, that is, a so-called coreless type roll in which the adhesive sheet 1 is wound alone. Alternatively, the adhesive sheet 1 before use may be in the form of a roll, or in the form of a laminate in which sheet-like (leaf-like) adhesive sheets are laminated with the adhesive layer surface of one adhesive sheet abutted against the back surface of another adhesive sheet, thereby protecting the adhesive surface 20A. Alternatively, the surface 20A of the adhesive sheet 1 before use may be protected by a release liner, not by the back surface of the substrate constituting the adhesive sheet.

[0021] In addition, when the adhesive sheet has a structure in which the adhesive layer is provided on both sides of the resin film substrate, the undercoat layer can be provided on both sides (first side and second side) of the resin film substrate. When the undercoat layer is provided on both sides of the resin film substrate, the adhesive sheet has the first adhesive layer, the first undercoat layer, the resin film substrate, the second undercoat layer, and the second adhesive layer in this order. Hereinafter, unless otherwise specified, the matters described for the adhesive layer are applied independently to the first adhesive layer and the second adhesive layer in an embodiment in which the resin film substrate has the first adhesive layer and the second adhesive layer on each side. Similarly, the matters described for the undercoat layer are applied independently to the first undercoat layer and the second undercoat layer in an embodiment in which the resin film substrate has the first undercoat layer and the second undercoat layer on each side.

[0022] <Adhesive layer> (Rubber Latex (A)) The adhesive layer is formed from an adhesive composition containing a rubber-based latex (A). As the rubber-based latex (A), either a natural rubber latex (A1) or a synthetic rubber latex (A2) can be used. Examples of the synthetic rubber latex (A2) include styrene-butadiene copolymer latex (SBR latex), nitrile rubber latex (NBR latex), and chloroprene latex. Such rubber-based latex (A) may be used alone or in combination of two or more. The rubber-based latex refers to a dispersion in which a rubber-based polymer such as natural rubber or synthetic rubber is dispersed in water, and the natural rubber latex and the synthetic rubber latex refer to dispersions in which natural rubber and synthetic rubber are dispersed in water, respectively.

[0023] In some embodiments, the adhesive composition contains natural rubber latex (A1). Adhesives formed using natural rubber tend to provide good adhesion to adherends. On the other hand, since natural rubber latex (A1) usually contains impurities such as proteins, an adhesive layer formed containing natural rubber latex (A1) is unlikely to provide good anchoring properties to resin films such as polyolefin-based resin films. However, the technology disclosed herein makes it possible to improve the anchoring properties of an adhesive layer formed containing natural rubber latex (A1).

[0024] The natural rubber contained in the natural rubber latex (A1) may be, for example, depolymerized or not depolymerized. The natural rubber may be unmodified natural rubber latex or modified natural rubber latex modified with, for example, an acrylic acid ester. Unmodified natural rubber latex and modified natural rubber latex may be used in combination. As the natural rubber latex (A1), a non-deproteinized natural rubber latex that has not been subjected to deproteinization treatment is usually used, but a deproteinized natural rubber latex that has been subjected to deproteinization treatment may also be used. The deproteinization treatment may be carried out by various known methods, such as a method of treating with a protease. The natural rubber may be used alone or in combination of two or more kinds.

[0025] In some preferred embodiments, unmodified natural rubber latex is used as the natural rubber latex (A1) from the viewpoints of adhesion, productivity, etc. In such embodiments, the proportion of unmodified natural rubber latex contained in the natural rubber latex (A1) is about 50% by weight or more (e.g., more than 50% by weight) based on the non-volatile content, may be about 70% by weight or more, may be about 90% by weight or more, or may be about 95% by weight or more, and the natural rubber contained in the natural rubber latex (A1) may be substantially composed of unmodified natural rubber.

[0026] In this specification, "X is substantially composed of Y" means that the ratio of Y in X is 97% by weight or more and 100% by weight or less, and preferably 99% by weight or more and 100% by weight or less, and does not exclude the unintentional inclusion of components other than Y in X.

[0027] In some preferred embodiments, a non-deproteinized natural rubber latex is used as the natural rubber latex (A1). By using a non-deproteinized natural rubber latex, the protein in the natural rubber latex (A1) reacts with the aqueous crosslinking agent (C), and high cohesive strength tends to be obtained. In such an embodiment, the proportion of the non-deproteinized natural rubber latex contained in the natural rubber latex (A1) is about 50% by weight or more (e.g., more than 50% by weight) based on the non-volatile content, and may be about 70% by weight or more, about 90% by weight or more, or about 95% by weight or more, and the natural rubber contained in the natural rubber latex (A1) may be substantially composed of non-deproteinized natural rubber. Although not particularly limited, the protein mass in the non-deproteinized natural rubber is about 0.2 to 0.7% by weight in terms of nitrogen content.

[0028] In an embodiment in which the rubber-based latex (A) contains a natural rubber latex (A1), the proportion of the natural rubber latex (A1) contained in the rubber-based latex (A) is not particularly limited, and may be, for example, about 10% by weight or more, or about 30% by weight or more, based on the non-volatile content. In some preferred embodiments, the proportion of the natural rubber latex (A1) contained in the rubber-based latex (A) is about 50% by weight or more (e.g., more than 50% by weight), about 70% by weight or more, about 90% by weight or more, or about 95% by weight or more, based on the non-volatile content, and the rubber latex (A) may be substantially composed of the natural rubber latex (A1).

[0029] In some embodiments, the adhesive composition contains a synthetic rubber latex (A2). An adhesive formed using the synthetic rubber latex (A2) tends to have better anchoring properties for resin films and the like than an adhesive formed using a natural rubber latex (A1). As the synthetic rubber latex (A2), any commercially available latex for adhesives and the like can be used without particular limitation. Both unmodified synthetic rubber latex and modified (e.g. acid-modified) synthetic rubber latex can be used. The synthetic rubber can be used alone or in combination of two or more types.

[0030] In some preferred embodiments, the synthetic rubber latex (A2) is, for example, an acid-modified synthetic rubber latex obtained by acid-modifying various synthetic rubber latexes such as SBR latex, NBR latex, and chloroprene latex. By using the acid-modified synthetic rubber latex, the pressure-sensitive adhesive layer can adhere well to an undercoat layer containing an oxazoline group described below, and can improve the anchoring property to the resin film substrate. In addition, by using the acid-modified synthetic rubber latex, the adhesion to an adherend such as a metal material is easily improved, and the cohesive force of the pressure-sensitive adhesive layer can be improved by a crosslinking reaction with the aqueous crosslinking agent (C) described below. As the acid-modified synthetic rubber latex, an acid-modified SBR latex is preferably used. As the acid-modified synthetic rubber latex, a synthetic rubber latex that has been acid-modified by a known or conventional method may be used. For example, an acid-modified synthetic rubber latex can be obtained by modifying the synthetic rubber in the latex with an unsaturated carboxylic acid such as acrylic acid, methacrylic acid, maleic acid, itaconic acid, or fumaric acid, or an anhydride of the unsaturated carboxylic acid. Alternatively, a commercially available product may be obtained as the acid-modified synthetic rubber latex. The acid-modified synthetic rubber may be used alone or in combination of two or more.

[0031] The presence or absence of acid modification of synthetic rubber latex can be confirmed by forming a film of the synthetic rubber latex and analyzing it by the ATR method (attenuated total reflection method) using FT-IR. As an analysis device, for example, "Nicolet iS10" manufactured by Thermo Fisher Scientific Inc. or an equivalent product can be used.

[0032] In an embodiment in which the synthetic rubber latex (A2) contains an acid-modified synthetic rubber latex, the proportion of the acid-modified synthetic rubber latex contained in the synthetic rubber latex (A2) is not particularly limited, and may be, for example, about 10% by weight or more, or about 30% by weight or more, based on the non-volatile content. In some preferred embodiments, from the viewpoint of effectively exerting the action of the acid-modified synthetic rubber latex, the proportion of the acid-modified synthetic rubber latex contained in the synthetic rubber latex (A2) is about 50% by weight or more (for example, more than 50% by weight), may be about 70% by weight or more, may be about 90% by weight or more, or may be about 95% by weight or more, based on the non-volatile content, and the synthetic rubber latex (A2) may be substantially composed of the acid-modified synthetic rubber latex.

[0033] The glass transition temperature (Tg) of the synthetic rubber (e.g., acid-modified synthetic rubber) contained in the synthetic rubber latex (A2) is not particularly limited. In some embodiments, the Tg of the synthetic rubber is preferably about -10°C or lower, more preferably about -20°C or lower, even more preferably about -30°C or lower, even more preferably about -40°C or lower, and particularly preferably about -50°C or lower, from the viewpoint of improving adhesion. In some embodiments, the lower limit of the Tg of the synthetic rubber is, for example, about -80°C or higher, may be about -70°C or higher, or may be about -65°C or higher. For the Tg of the synthetic rubber, the manufacturer's nominal value may be used for commercially available products. When the manufacturer's nominal value is unknown or the synthetic rubber obtained by synthesis is analyzed with a differential scanning calorimeter (DSC), the Tg of the synthetic rubber can be confirmed from the temperature of the inflection point of the obtained calorie curve. As the DSC, a product name "Q2000" manufactured by TA Instruments or an equivalent product can be used.

[0034] In an embodiment in which the rubber latex (A) contains the synthetic rubber latex (A2), the proportion of the synthetic rubber latex (A2) contained in the rubber latex (A) is not particularly limited, and may be, for example, about 1% by weight or more, about 5% by weight or more, or about 10% by weight or more, based on the non-volatile content. In some embodiments, from the viewpoint of effectively exerting the effect of containing the synthetic rubber latex, the proportion of the synthetic rubber latex (A2) contained in the rubber latex (A) may be about 30% by weight or more, about 50% by weight or more (for example, more than 50% by weight), about 70% by weight or more, about 90% by weight or more, or about 95% by weight or more, based on the non-volatile content, and the rubber latex (A) may be substantially composed of the synthetic rubber latex (A2). In some other embodiments, the proportion of the synthetic rubber latex (A2) contained in the rubber-based latex (A) may be about 90% by weight or less, about 70% by weight or less, about 50% by weight or less (e.g., less than 50% by weight), about 30% by weight or less, or about 10% by weight or less, based on the non-volatile content.

[0035] In some embodiments, the rubber-based latex (A) preferably contains a natural rubber latex (A1) and a synthetic rubber latex (A2). In such embodiments, the blending ratio of the natural rubber latex (A1) and the synthetic rubber latex (A2) is not particularly limited. The weight ratio (A1 / A2) of the natural rubber latex (A1) and the synthetic rubber latex (A2) may be, for example, 1 / 99 to 99 / 1, 10 / 90 to 99 / 1, or 30 / 70 to 99 / 1 based on the non-volatile content.

[0036] In some preferred embodiments, the natural rubber latex (A1) and the synthetic rubber latex (A2) are contained in the adhesive composition in such a ratio that the weight ratio (A1 / A2) is about 50 / 50 to 99 / 1 based on the non-volatile content. The weight ratio (A1 / A2) may be 60 / 40 to 99 / 1. By incorporating a predetermined amount of the synthetic rubber latex (A2) into the natural rubber latex (A1), the action of the synthetic rubber latex (A2) is effectively expressed while maintaining the adhesive properties (e.g., adhesion) based on the natural rubber latex (A1), and the adhesive is improved in cohesion and anchoring properties. Among them, it is particularly preferable to use the natural rubber latex (A1) in combination with an acid-modified synthetic rubber latex as the synthetic rubber latex (A2). Although it is not to be interpreted as being particularly limiting, it is considered that, in the case of using natural rubber latex (A1) alone, the reaction with the aqueous crosslinking agent (C) described later depends on the amount of protein in the natural rubber latex (A1), whereas by using an appropriate amount of acid-modified synthetic rubber latex (A2), the effect of the reaction with the aqueous crosslinking agent (C) (the effect based on the improvement of cohesive force) can be stably exhibited.

[0037] In some preferred embodiments, from the viewpoint of improving adhesion, the weight ratio (A1 / A2) of the natural rubber latex (A1) to the synthetic rubber latex (A2) is more preferably about 70 / 30 or more, even more preferably 75 / 25 or more, even more preferably 80 / 20 or more, particularly preferably 85 / 15 or more, and may be 90 / 10 or more, or may be 95 / 5 or more, based on the non-volatile content. In some embodiments, from the viewpoint of more effectively exerting the effect of containing the synthetic rubber, the weight ratio (A1 / A2) is 97 / 3 or less, 95 / 5 or less, 92 / 8 or less, 90 / 10 or less, or may be 80 / 20 or less, based on the non-volatile content.

[0038] Although not particularly limited, in an embodiment in which a natural rubber latex (A1) and a synthetic rubber latex (A2) are used in combination as the rubber-based latex (A), the total proportion of the natural rubber latex (A1) and the synthetic rubber latex (A2) in the rubber-based latex (A) is preferably about 70% by weight or more, more preferably about 90% by weight or more, and even more preferably about 95% by weight or more, based on the non-volatile content. It is particularly preferable that the rubber-based latex (A) is substantially composed of the natural rubber latex (A1) and the synthetic rubber latex (A2) based on the non-volatile content.

[0039] (Tackifier (B)) In some embodiments, the pressure-sensitive adhesive composition preferably contains a tackifier (B). The use of the tackifier (B) can improve the adhesiveness of the pressure-sensitive adhesive layer. The tackifier (B) is typically blended in the pressure-sensitive adhesive composition in the form of a tackifier emulsion from the viewpoint of compatibility. In this specification, the term "tackifier emulsion" refers to a dispersion liquid in which a tackifier is dispersed in water. Examples of the tackifier (B) include petroleum-based tackifiers, rosin-based resins, rosin derivative resins, terpene-based resins, ketone-based resins, and xylene-based resins. The tackifier (B) can be used alone or in combination of two or more.

[0040] In some preferred embodiments, the pressure-sensitive adhesive composition contains a petroleum-based tackifier emulsion as the tackifier (B). The petroleum-based tackifier emulsion (B) is well compatible with the rubber-based latex (A), causes little contamination of the adherend, and can favorably improve the adhesiveness of the pressure-sensitive adhesive layer. Examples of the petroleum-based tackifier contained in the petroleum-based tackifier emulsion include aliphatic hydrocarbon resins, aromatic hydrocarbon resins, aliphatic / aromatic hydrocarbon resins, and hydrogenated products thereof. Examples of aliphatic hydrocarbon resins include homopolymers, copolymers, and hydrogenated products thereof (so-called C5 petroleum resins, etc.) of mainly C5 fractions (piperylene, piperylene, isoprene, 2-methyl-2-butene, dicyclopentadiene, etc.) from the cracked fractions of petroleum naphtha. Examples of aromatic hydrocarbon resins include homopolymers and copolymers of mainly C9 fractions (styrene, methylstyrene, indene, methylindene, coumarone, etc.) from the cracked fractions of petroleum naphtha, and hydrogenated products thereof (so-called C9 petroleum resins, etc.). Examples of aliphatic / aromatic hydrocarbon resins include copolymers of mainly C5 fractions and C9 fractions from the cracked fractions of petroleum naphtha, and hydrogenated products thereof (so-called C5-C9 copolymerized petroleum resins, etc.). Among these, aliphatic hydrocarbon resins and hydrogenated products of aliphatic / aromatic hydrocarbon resins are preferred, and aliphatic hydrocarbon resins are particularly preferred. The petroleum tackifiers can be used alone or in combination of two or more.

[0041] In an embodiment in which the PSA composition contains a petroleum-based tackifier emulsion as the tackifier (B), the proportion of the petroleum-based tackifier emulsion contained in the tackifier (B) is not particularly limited and may be, for example, about 10% by weight or more, or about 30% by weight or more, based on the non-volatile content. In some preferred embodiments, from the viewpoint of effectively exerting the action of the petroleum-based tackifier emulsion, the proportion of the petroleum-based tackifier emulsion contained in the tackifier (B) is about 50% by weight or more (e.g., more than 50% by weight), may be about 70% by weight or more, may be about 90% by weight or more, or may be about 95% by weight or more, based on the non-volatile content, and the tackifier (B) may be substantially composed of the petroleum-based tackifier emulsion.

[0042] In some other embodiments, the pressure-sensitive adhesive composition contains a rosin-based tackifier emulsion as the tackifier (B). The rosin-based tackifier emulsion is well compatible with the rubber-based latex (A) and can improve the adhesiveness of the pressure-sensitive adhesive layer. For example, the rosin-based tackifier emulsion is well compatible with the pressure-sensitive adhesive composition containing a synthetic rubber latex (A2) as the rubber-based latex (A), and can preferably exhibit an adhesiveness-improving effect. Examples of the rosin-based tackifier contained in the rosin-based tackifier emulsion include unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; modified rosins (hydrogenated rosin, disproportionated rosin, polymerized rosin, other chemically modified rosins, etc.) obtained by modifying the unmodified rosin through hydrogenation treatment, disproportionation treatment, polymerization, etc.; and various other rosin derivatives. Examples of the rosin derivatives include rosin esters and rosin phenols. Examples of the rosin esters include rosin esters obtained by esterification of unmodified or modified rosin with polyhydric alcohol; polyhydric alcohol esters of unsaturated fatty acid modified rosin obtained by partially modifying unmodified or modified rosin with unsaturated fatty acid (fumaric acid, maleic acid, etc.) and then esterifying; polyhydric alcohol esters of unsaturated fatty acid modified disproportionated rosin obtained by partially modifying unmodified or modified rosin with unsaturated fatty acid, disproportionating, and then esterifying. Examples of the rosin phenols include those obtained by adding phenols to rosins and thermally polymerizing them; those obtained by esterifying the thermal polymers; and the like. The polyhydric alcohol used in the esterification is not particularly limited, and various known polyhydric alcohols such as diethylene glycol, glycerin, trimethylolpropane, trimethylolethane, 1,2,6-hexanetriol, 1,2,4-butanetriol, and pentaerythritol can be used. The rosin-based tackifiers can be used alone or in combination of two or more.

[0043] The softening point of the tackifier (B) is not particularly limited, and for example, a suitable tackifier having a softening point in the range of about 60°C to 200°C can be used. In some embodiments, the softening point of the tackifier (B) may be about 180°C or less, about 160°C or less, or about 140°C or less. A tackifier (B) having a softening point of a predetermined value or less tends to produce a pressure-sensitive adhesive having good adhesion to an adherend. In some embodiments, the softening point of the tackifier (B) is about 70°C or more, about 80°C or more, or about 90°C or more. By using a tackifier (B) having a softening point of a predetermined value or more, the adhesive transfer prevention property can be improved.

[0044] In some preferred embodiments, from the viewpoint of obtaining high adhesiveness, a tackifier having a softening point of 120° C. or less (hereinafter, may be referred to as a "low softening point tackifier") is used as the tackifier (B). By using a tackifier having a low softening point, compatibility with rubber-based latex can also be improved. The softening point of the low softening point tackifier is more preferably about 115° C. or less, even more preferably about 110° C. or less, particularly preferably about 105° C. or less, and may be about 100° C. or less. In addition, from the viewpoint of preventing adhesive residue, the softening point of the low softening point tackifier is preferably about 60° C. or more, more preferably about 80° C. or more, even more preferably about 90° C. or more, and may be about 95° C. or more. Although not particularly limited, the above-mentioned petroleum-based tackifier and rosin-based tackifier are preferably used as the low softening point tackifier. Among them, it is more preferable to use an aliphatic hydrocarbon resin. The low softening point tackifiers can be used alone or in combination of two or more.

[0045] In some embodiments, the tackifier (B) may or may not include one or more tackifiers having a softening point higher than 120° C. (hereinafter, sometimes referred to as "high softening point tackifiers"). For example, the high softening point tackifier may be used in combination with the low softening point tackifier. Alternatively, only the high softening point tackifier may be used as the tackifier (B).

[0046] In an embodiment in which a low-softening point tackifier is used as the tackifier (B), the proportion of the low-softening point tackifier in the entire tackifier (B) is not particularly limited, and may be, for example, about 10% by weight or more, about 30% by weight or more, or about 50% by weight or more. In some preferred embodiments, from the viewpoint of effectively exerting the effect of using the low-softening point tackifier, the proportion of the low-softening point tackifier in the entire tackifier (B) is more than 50% by weight, more preferably about 70% by weight or more, even more preferably about 90% by weight or more, and particularly preferably about 95% by weight or more. The tackifier (B) may be substantially composed of the low-softening point tackifier.

[0047] In this specification, the softening point of a petroleum-based tackifier is defined as a value measured based on the softening point test method (ring and ball method) specified in JIS K5902 and JIS K2207. Specifically, the sample is melted as quickly as possible at a low temperature, and then filled into a ring placed on a flat metal plate, taking care not to create bubbles. After cooling, the part that protrudes from the flat surface, including the top end of the ring, is cut off with a slightly heated knife. Next, a holder (ring stand) is placed in a glass container (heating bath) with a diameter of 85 mm or more and a height of 127 mm or more, and glycerin is poured in until it is 90 mm or more deep. Next, a steel ball (diameter 9.5 mm, weight 3.5 g) and the ring filled with the sample are immersed in glycerin without touching each other, and the temperature of the glycerin is kept at 20°C ± 5°C for 15 minutes. Next, the steel ball is placed in the center of the surface of the sample in the ring, and this is placed in a fixed position on the holder. Next, keeping the distance from the top of the ring to the glycerin surface at 50 mm, place a thermometer and align the center of the thermometer's mercury bulb to the same height as the center of the ring, then heat the container. The flame of the Bunsen burner used for heating should be midway between the center of the bottom of the container and its edge, and heating should be uniform. After heating begins and the temperature of the bath reaches 40°C, the rate of increase must be 5.0 ± 0.5°C per minute. The sample gradually softens and flows down the ring, and the temperature is read when it finally touches the bottom plate, and this is the softening point. The softening point is measured for two or more samples at the same time, and the average value is used.

[0048] The tackifier emulsion that can be used as the tackifier (B) can be prepared by appropriately adopting a known tackifier resin emulsification method, or a commercially available tackifier emulsion can be used. Examples of the emulsification method include a high-pressure emulsification method and an inversion emulsification method. The high-pressure emulsification method can be carried out, for example, by adding water and a suitable emulsifier to a solution obtained by dissolving a tackifier in a solvent (typically benzene, toluene, etc.), emulsifying using a high-pressure emulsifier, and then removing the solvent (for example, by distilling off under reduced pressure) as necessary. Alternatively, a tackifier emulsion can be prepared without substantially using an organic solvent by heating a tackifier to a temperature above its softening point to make it in a molten state, mixing this with water and a suitable emulsifier, and emulsifying using a high-pressure emulsifier (solvent-free high-pressure emulsification method). The inversion emulsification method can be carried out, for example, by mixing a small amount of a solvent (benzene, toluene, etc.) with a tackifier, kneading in an appropriate emulsifier, and gradually adding hot water to cause phase inversion emulsification to form an emulsion. Alternatively, a tackifier emulsion can be prepared without substantially using an organic solvent by raising the temperature of the tackifier to or above its softening point, kneading in an emulsifier, and gradually adding hot water to cause phase inversion emulsification (solvent-free phase inversion emulsification method).

[0049] The emulsifier used for emulsifying the tackifier is not particularly limited, and may be appropriately selected from known emulsifiers. For example, anionic emulsifiers and nonionic emulsifiers may be used. Examples of anionic emulsifiers include alkyl sulfate type anionic emulsifiers such as sodium lauryl sulfate, ammonium lauryl sulfate, and potassium lauryl sulfate; polyoxyethylene alkyl ether sulfate type anionic emulsifiers such as sodium polyoxyethylene lauryl ether sulfate; polyoxyethylene alkyl phenyl ether sulfate type anionic emulsifiers such as ammonium polyoxyethylene lauryl phenyl ether sulfate and sodium polyoxyethylene lauryl phenyl ether sulfate; sulfonate type anionic emulsifiers such as sodium dodecylbenzenesulfonate; sulfosuccinic acid type anionic emulsifiers such as disodium lauryl sulfosuccinate and disodium polyoxyethylene lauryl sulfosuccinate; and the like. Examples of nonionic emulsifiers include polyoxyethylene alkyl ether type nonionic emulsifiers such as polyoxyethylene lauryl ether; polyoxyethylene alkyl phenyl ether type nonionic emulsifiers such as polyoxyethylene lauryl phenyl ether; polyoxyethylene fatty acid esters, polyoxyethylene polyoxypropylene block polymers, etc. In some embodiments, a salt of rosin may be used as the emulsifier. For example, from the viewpoint of ease of emulsification and stability over time of the emulsion, an ammonium salt of rosin containing 50% by weight or more of dihydroabietic acid is preferably used.

[0050] Although not particularly limited, it is preferable that the emulsification of the tackifier is carried out using the above emulsifier in the presence of a protective colloid such as a water-soluble salt of casein. The water-soluble salt of casein is not particularly limited, and is used in the form of an aqueous casein solution in which casein is dissolved in an aqueous solution of a basic compound (sodium hydroxide, potassium hydroxide, ammonia, organic amines, etc.). For example, an aqueous ammonium casein solution is preferably used.

[0051] In an embodiment in which the adhesive composition contains a tackifier (B), the content of the tackifier (B) in the adhesive composition, and therefore in the adhesive layer, is not particularly limited. For example, the content of the tackifier (B) relative to 100 parts by weight of the rubber latex (A) may be about 1 part by weight or more, about 10 parts by weight or more, or about 30 parts by weight or more, based on the non-volatile content. From the viewpoint of obtaining higher adhesion, in some preferred embodiments, the content of the tackifier (B) relative to 100 parts by weight of the rubber latex (A) is about 50 parts by weight or more, more preferably about 55 parts by weight or more, even more preferably about 60 parts by weight or more, particularly preferably about 65 parts by weight or more, and may be about 70 parts by weight or more, about 80 parts by weight or more, or about 90 parts by weight or more, based on the non-volatile content. In some embodiments, the content of the tackifier (B) relative to 100 parts by weight of the rubber latex (A) may be about 150 parts by weight or less, about 130 parts by weight or less, about 120 parts by weight or less, or about 110 parts by weight or less, based on the non-volatile content. By appropriately limiting the content of the tackifier (B) within the above range, the tackifier (B) is easily compatible with the rubber latex (A) and good adhesive properties are easily obtained. In some preferred embodiments, the content of the tackifier (B) relative to 100 parts by weight of the rubber latex (A) may be about 100 parts by weight or less, about 95 parts by weight or less, about 90 parts by weight or less, about 85 parts by weight or less, about 80 parts by weight or less, or about 75 parts by weight or less, based on the non-volatile content. By setting the content of the tackifier (B) within the above range, it is possible to improve the peelability from the adherend while maintaining sufficient adhesion. For example, the decrease in the cohesive strength of the adhesive layer is suppressed, and there is a tendency for the adhesive layer to have excellent resistance to adhesive residue and contamination of the adherend after peeling the adhesive from the adherend. In addition, by limiting the amount of tackifier (B) used, it is possible to prevent the peel strength from the adherend from becoming excessively high, and it is possible to improve the workability when peeling from the adherend. For example, peeling defects such as the adhesive sheet being torn during peeling are also easily prevented.

[0052] (Water-based crosslinker (C)) The adhesive composition contains an aqueous crosslinking agent (C). Here, the aqueous crosslinking agent is a concept that includes water-dispersible crosslinking agents and water-soluble crosslinking agents. The use of the aqueous crosslinking agent (C) can impart an appropriate cohesive force to the adhesive layer. As the aqueous crosslinking agent (C), it is preferable to use an aqueous crosslinking agent having at least one functional group selected from an oxazoline group, an isocyanate group, and an epoxy group. By blending the aqueous crosslinking agent having the specific functional group with the adhesive composition containing the rubber latex (A), the adhesive layer formed from the adhesive composition can adhere well to the undercoat layer containing an oxazoline group described below, and can improve the anchoring ability to the resin film substrate. As the aqueous crosslinking agent (C), an oxazoline-based crosslinking agent, an isocyanate-based crosslinking agent, or an epoxy-based crosslinking agent can be used. The aqueous crosslinking agent (C) can be used alone or in combination of two or more types.

[0053] As the oxazoline crosslinking agent, a compound having one or more oxazoline groups in one molecule can be used. The oxazoline group may be any of 2-oxazoline group, 3-oxazoline group, and 4-oxazoline group. An oxazoline crosslinking agent having a 2-oxazoline group can be preferably used. For example, a water-soluble copolymer or a water-dispersed copolymer obtained by copolymerizing an addition polymerizable oxazoline such as 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline with another monomer can be used as the oxazoline crosslinking agent. As the oxazoline crosslinking agent, either water-soluble or water-dispersed type can be used, but a water-soluble oxazoline crosslinking agent is preferably used. Commercially available oxazoline-based crosslinking agents include, for example, products manufactured by Nippon Shokubai Co., Ltd. under the trade names "Epocross WS-500," "Epocross WS-700," "Epocross K-2010E," "Epocross K-2020E," and "Epocross K-2035E."

[0054] Examples of isocyanate crosslinking agents include polyfunctional isocyanate compounds having two or more functionalities. Examples of isocyanate crosslinking agents include aromatic isocyanates such as tolylene diisocyanate, xylene diisocyanate, polymethylene polyphenyl diisocyanate, tris(p-isocyanatophenyl)thiophosphate, and diphenylmethane diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; and aliphatic isocyanates such as hexamethylene diisocyanate. As the isocyanate crosslinking agent, either water-soluble or water-dispersible isocyanate crosslinking agents may be used. As the isocyanate crosslinking agent, a so-called blocked isocyanate type isocyanate crosslinking agent in which the isocyanate group is blocked may be used. Examples of commercially available products include the "Burnoc DNW" series manufactured by DIC Corporation, the "Aquanate" series manufactured by Tosoh Corporation, the "Takenate WD" series manufactured by Mitsui Chemicals, Inc., and the "Elastron BN" series manufactured by Daiichi Kogyo Seiyaku Co., Ltd.

[0055] As the epoxy crosslinking agent, a compound having two or more epoxy groups in one molecule can be used. An epoxy crosslinking agent having 3 to 5 epoxy groups in one molecule is preferred. As the epoxy crosslinking agent, either water-soluble or water-dispersible type can be used, but a water-soluble epoxy crosslinking agent is preferably used. Specific examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, (poly)ethylene glycol diglycidyl ether, glycerol polyglycidyl ether, polyglycerol polyglycidyl ether, and the like. Commercially available epoxy crosslinking agents include those available under the trade name "Epicron CR-5L" manufactured by DIC Corporation, and those available under the trade names "Denacol EX-313," "Denacol EX-512," "Denacol EX-810," "Denacol EX-821," "Denacol EX-830," and "Denacol EX-850" manufactured by Nagase ChemteX Corporation.

[0056] In some preferred embodiments, at least one selected from an oxazoline-based crosslinking agent and an epoxy-based crosslinking agent is used as the aqueous crosslinking agent (C). Compared with, for example, an isocyanate-based crosslinking agent, an oxazoline-based crosslinking agent and an epoxy-based crosslinking agent have good stability in the adhesive composition and are advantageous in terms of productivity. In addition, an oxazoline-based crosslinking agent and an epoxy-based crosslinking agent are more likely to provide excellent adhesive transfer prevention properties. From this viewpoint, in some embodiments, the total ratio of the oxazoline-based crosslinking agent and the epoxy-based crosslinking agent to the total amount of the aqueous crosslinking agent (C) contained in the adhesive composition may be approximately 10% by weight or more, approximately 30% by weight or more, or approximately 50% by weight or more, based on the non-volatile content. In some preferred embodiments, the total ratio of the oxazoline-based crosslinking agent and the epoxy-based crosslinking agent to the total amount of the aqueous crosslinking agent (C) is more than 50% by weight, more preferably approximately 70% by weight or more, even more preferably approximately 90% by weight or more, and particularly preferably approximately 95% by weight or more, based on the non-volatile content. The aqueous crosslinking agent (C) may be substantially composed of at least one selected from an oxazoline-based crosslinking agent and an epoxy-based crosslinking agent.

[0057] In some embodiments, it is particularly preferable to use an oxazoline-based crosslinking agent as the aqueous crosslinking agent (C). The oxazoline-based crosslinking agent can react at a relatively low heating temperature of about 80° C., so that the desired adhesive properties are developed early, and the adhesive properties have good stability over time. It is also suitable when the heating temperature is limited during the preparation of the adhesive sheet, such as when a polyolefin-based resin film is used. In addition, the oxazoline-based crosslinking agent is also advantageous in that it can efficiently increase the degree of crosslinking with a relatively small amount of use. Furthermore, the adhesive layer formed using the oxazoline-based crosslinking agent is likely to have good processability. From this viewpoint, in some embodiments, the ratio of the oxazoline-based crosslinking agent to the total amount of the aqueous crosslinking agent (C) contained in the adhesive composition may be about 10% by weight or more, about 30% by weight or more, or about 50% by weight or more based on the non-volatile content. In some preferred embodiments, the proportion of the oxazoline-based crosslinking agent in the total amount of the aqueous crosslinking agent (C) is more than 50% by weight, more preferably about 70% by weight or more, even more preferably about 90% by weight or more, and particularly preferably about 95% by weight or more, based on the non-volatile content. The aqueous crosslinking agent (C) may be substantially composed of the oxazoline-based crosslinking agent.

[0058] In some embodiments, it is preferable that the aqueous crosslinking agent (C) does not contain an isocyanate-based crosslinking agent or that the amount of the isocyanate-based crosslinking agent used is limited. This can suppress the short pot life and gelation during storage caused by the inclusion of a relatively highly active isocyanate-based crosslinking agent, and can improve productivity. From this viewpoint, in some embodiments, the proportion of the isocyanate-based crosslinking agent in the total amount of the aqueous crosslinking agent (C) contained in the pressure-sensitive adhesive composition may be approximately 50% by weight or less (for example, less than 50% by weight), approximately 30% by weight or less, approximately 10% by weight or less, approximately 3% by weight or less, or approximately 1% by weight or less. The aqueous crosslinking agent (C) may not substantially contain an isocyanate-based crosslinking agent.

[0059] In addition, the pressure-sensitive adhesive composition may or may not contain, as the aqueous crosslinking agent (C), other aqueous crosslinking agents than the aqueous crosslinking agent having at least one functional group selected from an oxazoline group, an isocyanate group, and an epoxy group, within the scope of not impairing the effects of the technology disclosed herein. Examples of such other aqueous crosslinking agents include aziridine-based crosslinking agents, carbodiimide-based crosslinking agents, metal chelate-based crosslinking agents, etc. The other aqueous crosslinking agents may be used alone or in combination of two or more.

[0060] The content of the aqueous crosslinking agent (C) in the adhesive composition is not particularly limited, and may be an appropriate amount that exhibits the desired anchoring improvement effect. In some embodiments, the content of the aqueous crosslinking agent (C) in the adhesive composition, and therefore in the adhesive layer, may be about 0.01 parts by weight or more relative to 100 parts by weight of the rubber latex (A) on a non-volatile basis. In some preferred embodiments, the content of the aqueous crosslinking agent (C) is about 0.1 parts by weight or more relative to 100 parts by weight of the rubber latex (A) on a non-volatile basis, more preferably about 0.3 parts by weight or more, even more preferably about 0.5 parts by weight or more, even more preferably 0.8 parts by weight or more, particularly preferably 1.0 parts by weight or more, and may be about 2.0 parts by weight or more, 3.0 parts by weight or more, or 4.0 parts by weight or more. The adhesive layer containing a predetermined amount or more of the aqueous crosslinking agent (C) can adhere well to the undercoat layer containing a water-dispersible polymer having an oxazoline group, and can exhibit good anchoring properties. In addition, by containing a predetermined amount or more of the aqueous crosslinking agent (C), the adhesive layer has a moderate cohesive force and is less likely to leave adhesive residue. For example, when an acid-modified synthetic rubber latex is used as the rubber latex (A), the acid in the acid-modified synthetic rubber latex reacts well with the crosslinkable reactive group of the aqueous crosslinking agent (C), and the resulting adhesive layer has a moderate cohesive force and is less likely to leave adhesive residue. In some embodiments, the content of the aqueous crosslinking agent (C) may be about 10 parts by weight or less, about 8 parts by weight or less, or about 6 parts by weight or less, based on the non-volatile content, relative to 100 parts by weight of the rubber-based latex (A). By appropriately limiting the amount of the aqueous crosslinking agent (C) used, contamination of the adherend surface after removal of the adhesive is easily prevented. Also, the peel strength can be adjusted by using an appropriate amount of the aqueous crosslinking agent (C). In some preferred embodiments, the content of the aqueous crosslinking agent (C) is about 5.0 parts by weight or less, or may be about 4.0 parts by weight or less, or may be about 3.5 parts by weight or less, or may be about 3.0 parts by weight or less, or may be about 2.5 parts by weight or less, or may be about 2.0 parts by weight or less, or may be about 1.5 parts by weight or less, based on the non-volatile content, relative to 100 parts by weight of the rubber latex (A). By setting the amount of the aqueous crosslinking agent (C) used within the above range, the peel strength can be suppressed and the peelability from the adherend can be improved.

[0061] (Laser light absorber) The adhesive layer may contain a laser beam absorbent as necessary, or may not contain the laser beam absorbent. By containing a laser beam absorbent in the adhesive layer, the adhesive layer can be made into a laser beam absorbing layer, and the cutting property by laser beam can be improved. As the laser beam absorbent that can be contained in the adhesive layer, one or more types can be appropriately selected from the laser beam absorbents exemplified below. In an embodiment in which the adhesive layer contains a laser beam absorbent, the content of the laser beam absorbent in the adhesive layer is usually 5% by weight or less, and from the viewpoint of adhesive performance, it is preferably 3% by weight or less, and may be 1% by weight or less. Alternatively, the technology disclosed herein can be preferably implemented in an embodiment in which the adhesive layer does not substantially contain a laser beam absorbent.

[0062] (Anti-aging agent) The adhesive layer may contain an antioxidant as necessary. The quality stability of the adhesive may be improved by using an antioxidant. The antioxidant may be used alone or in combination of two or more. Examples of the antioxidant include phosphorus-based antioxidants, phenol-based antioxidants, hindered amine-based antioxidants, aromatic amine-based antioxidants, and sulfur-based antioxidants. Although not particularly limited, the amount of the antioxidant contained in the adhesive layer may be, for example, approximately 20 parts by weight or less, and usually 10 parts by weight or less is appropriate, and may be 5 parts by weight or less, based on the non-volatile content, based on 100 parts by weight of the rubber-based latex (A). In addition, the amount of the antioxidant may be, for example, 0.1 parts by weight or more, may be 0.5 parts by weight or more, or may be 1 part by weight or more, based on the non-volatile content, based on 100 parts by weight of the rubber-based latex (A).

[0063] (optional ingredient) The adhesive layer may contain various additives that can be used in the field of adhesives, such as viscosity adjusters (thickeners, etc.), leveling agents, dispersants, plasticizers, softeners, fillers, colorants such as pigments and dyes, light stabilizers, antioxidants, water-resistant agents, antifoaming agents, preservatives, and crosslinking assistants, as necessary. The dispersant is preferably one that can function as a protective colloid, and water-soluble polymers such as gelatin, polyvinyl alcohol, polyvinyl alcohol derivatives, water-soluble salts of cellulose, cellulose derivatives, and polyacrylic acid (salts) without hydrophobic side chains can be used. The adhesive layer may also contain an emulsifier as necessary. As such an emulsifier, for example, those exemplified as emulsifiers that can be used for emulsifying a tackifier emulsion can be used.

[0064] (Water-dispersible pressure-sensitive adhesive composition) Since the adhesive composition disclosed herein can be prepared using an aqueous component as described above, it is possible to substantially not use an organic solvent or to reduce the amount of organic solvent used. This is significant in terms of eliminating organic solvents and being environmentally friendly. The adhesive composition can typically be implemented in the form of an aqueous dispersion type adhesive composition containing a rubber latex and an aqueous crosslinking agent. In this specification, the aqueous dispersion type adhesive composition refers to a composition in which at least a part of the adhesive-forming components is dispersed in water. The aqueous dispersion type also includes a suspended state and an emulsified state. Therefore, the concept of the aqueous dispersion type adhesive composition includes what is called an emulsion type adhesive composition. The aqueous dispersion type adhesive composition contains water as a dispersion medium or solvent. The aqueous dispersion type adhesive composition may also contain a liquid other than water as necessary. The liquid other than water may be, for example, one or more selected from various organic solvents (such as lower alcohols) that can be uniformly mixed with water. Generally, the proportion of water in the volatile components contained in the water-dispersed pressure-sensitive adhesive composition is, for example, 90% by weight or more, and preferably 95 to 100% by weight. In this specification, a pressure-sensitive adhesive (layer) formed from the water-dispersed pressure-sensitive adhesive composition is also referred to as a water-dispersed pressure-sensitive adhesive (layer).

[0065] In addition, the adhesive composition (typically, a water-dispersed adhesive composition) used for forming the adhesive layer preferably does not substantially contain an organic solvent from the viewpoint of environmental consideration and removal of organic solvents. Here, "the adhesive composition does not substantially contain an organic solvent" means that the amount of the organic solvent in the adhesive composition is less than 1% by weight (e.g., less than 0.1% by weight).

[0066] Although not particularly limited, in some embodiments, the adhesive composition may be a composition in which the total amount of the rubber latex (A), the tackifier (B), and the aqueous crosslinking agent (C) accounts for 70% by weight or more of the total weight of the adhesive composition based on the non-volatile content (i.e., the weight of the adhesive layer constituted by this adhesive). This allows the effects of containing the above-mentioned (A), (B), and (C) components to be suitably exhibited. In some preferred embodiments, the total amount of the above-mentioned (A), (B), and (C) components may be 80% by weight or more, 90% by weight or more (e.g., 90 to 100% by weight), or 95% by weight or more (e.g., 95 to 100% by weight) of the total weight of the adhesive composition based on the non-volatile content. The adhesive composition having the above composition allows the effects of the technology disclosed herein to be suitably realized.

[0067] (Formation of adhesive layer) The pressure-sensitive adhesive layer can be formed, for example, by applying (typically applying) any of the pressure-sensitive adhesive compositions disclosed herein to an undercoat layer provided on a resin film substrate or a release liner, and drying the composition. The pressure-sensitive adhesive layer formed on the release liner can be transferred to the surface of the undercoat layer on the resin film substrate to produce a pressure-sensitive adhesive sheet. The pressure-sensitive adhesive composition can be applied using a known or conventional coater, such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, or a spray coater. From the viewpoint of promoting the crosslinking reaction, improving the production efficiency, etc., it is preferable to dry the pressure-sensitive adhesive composition under heating. For example, a drying temperature of about 40 to 120°C, about 40 to 100°C, or about 40 to 80°C can be adopted. After drying the pressure-sensitive adhesive composition, aging may be performed, for example, within a range of room temperature or higher and about 60°C or lower, for the purpose of adjusting the component migration in the pressure-sensitive adhesive layer, advancing the crosslinking reaction, and relaxing distortion that may exist in the pressure-sensitive adhesive sheet.

[0068] (Adhesive layer thickness) The thickness of the adhesive layer can be appropriately set so as to obtain an appropriate adhesive performance depending on the application of the adhesive sheet, and is usually appropriate to be about 0.5 μm to 200 μm. From the viewpoint of improving adhesion to the adherend, in some preferred embodiments, the thickness of the adhesive layer may be, for example, 1.5 μm or more, 3 μm or more, 5 μm or more, 7 μm or more, or 10 μm or more. In addition, the thickness of the adhesive layer may be, for example, about 150 μm or less, or about 100 μm or less. By limiting the thickness of the adhesive layer, the adhesive sheet can be made thinner. In addition, limiting the thickness of the adhesive layer is also preferable in terms of preventing the occurrence of adhesive residue due to cohesive failure of the adhesive layer. In some preferred embodiments, the thickness of the adhesive layer is about 50 μm or less, 30 μm or less, 20 μm or less, 18 μm or less, 16 μm or less, or 15 μm or less. The above-mentioned small thickness of the adhesive layer can be advantageous, for example, in terms of the speed and precision of laser processing in an adhesive sheet that can be used in a manner in which it is laser cut together with an adherend (workpiece).

[0069] <Resin film substrate> The adhesive sheet includes a resin film as a substrate. The adhesive sheet having a resin film substrate can improve productivity, handling, processability, etc. In addition, the adhesive sheet having a resin film substrate can have good removability from the adherend. Here, the term "resin film" refers to a resin film having a non-porous structure, typically substantially free of air bubbles (voidless). Therefore, the above-mentioned resin film is a concept that is distinguished from foam films and nonwoven fabrics. Examples of resin materials constituting the resin film include polyester resins such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT); polyolefin resins such as polyethylene, polypropylene, ethylene-propylene copolymer, and polypropylene-polyethylene blend resin; and others, including, but not limited to, vinyl chloride resins (typically soft vinyl chloride resins), vinyl acetate resins, and polyamide-based resins.

[0070] In some embodiments, from the viewpoint of various processability due to the flexibility of the resin film substrate, or from the viewpoint of, for example, the cuttability and non-contamination of the pressure-sensitive adhesive sheet by a specific laser beam, a polyolefin-based resin film or a polyester-based resin film can be preferably used as the resin film. Among them, from the viewpoint of conformity to the adherend, a polyolefin-based resin film is preferred. Pressure-sensitive adhesive compositions containing rubber-based latex such as natural rubber latex tend to have reduced anchoring properties with respect to polyolefin-based resin film substrates, but according to the technology disclosed herein, a polyolefin-based resin film substrate can be used to obtain good anchoring properties while enjoying the advantages of polyolefin-based resin films.

[0071] Here, the polyolefin resin film refers to a resin film whose main component is a polyolefin resin. In this specification, the main component refers to a component contained in an amount of more than 50% by weight, unless otherwise specified. For example, when the main component of a resin film is a polyolefin resin, the resin film contains a polyolefin resin in an amount of more than 50% by weight of its total weight. A suitable example of a polyolefin resin film is a resin film whose main component is a polyethylene (PE) resin and / or a polypropylene (PP) resin. A polyolefin resin film contains a PE resin and / or a PP resin, and the total amount of the PE resin and the PP resin may be more than 50% by weight of the polyolefin resin film, preferably 70% by weight or more, for example 85% by weight or more. The above total amount corresponds to the content of the PE resin in a resin film containing a PE resin and not a PP resin.

[0072] The PE resin may be mainly composed of various polymers (ethylene-based polymers) having ethylene as the main constituent monomer unit. The PE resin may be substantially composed of one or more ethylene-based polymers. The ethylene-based polymer may be a homopolymer of ethylene, or may be a copolymer of ethylene as the main monomer with another α-olefin as a secondary monomer (random copolymerization, block copolymerization, etc.). Suitable examples of the α-olefin include α-olefins having 3 to 10 carbon atoms, such as propylene, 1-butene (which may be branched 1-butene), 1-hexene, 4-methyl-1-pentene, and 1-octene. For example, a PE resin mainly composed of an ethylene-based polymer copolymerized with the α-olefin as a secondary monomer at a ratio of 10% by weight or less (typically 5% by weight or less) may be preferably used.

[0073] The PE resin may also be a PE resin containing a copolymer of ethylene and a monomer (functional group-containing monomer) having another functional group in addition to the polymerizable functional group, or a PE resin in which such a functional group-containing monomer is copolymerized with an ethylene-based polymer, etc. Examples of copolymers of ethylene and functional group-containing monomers include ethylene-vinyl acetate copolymer (EVA), ethylene-acrylic acid copolymer (EAA), ethylene-methacrylic acid copolymer (EMAA), ethylene-methyl acrylate copolymer (EMA), ethylene-ethyl acrylate copolymer (EEA), ethylene-methyl methacrylate copolymer (EMMA), and ethylene-(meth)acrylic acid (i.e., acrylic acid and / or methacrylic acid) copolymers crosslinked with metal ions.

[0074] The density of the PE resin is not particularly limited. The concept of PE resin here includes high density polyethylene (HDPE), medium density polyethylene (MDPE), low density polyethylene (LDPE) and linear low density polyethylene (LLDPE). In some embodiments, the density of the PE resin is, for example, 0.90 to 0.94 g / cm. 3 Preferred PE resins include LDPE and LLDPE.

[0075] The PP resin may be a polymer (propylene-based polymer) having propylene as the main constituent monomer unit, i.e., a polymer having more than 50% by weight of all constituent monomer units being propylene as the main component. The PP resin may be substantially composed of one or more propylene-based polymers. The concept of propylene-based polymer here includes homopolypropylene, as well as random copolymers (random polypropylenes) and block copolymers (block polypropylenes) of propylene and other monomers.

[0076] The first surface of the resin film substrate (i.e., the surface on which the pressure-sensitive adhesive layer is provided) may be subjected to an appropriate surface treatment to enhance adhesion to the undercoat layer, as necessary. Examples of surface treatments to enhance adhesion include corona discharge treatment, acid treatment, ultraviolet irradiation treatment, plasma treatment, etc.

[0077] In some preferred embodiments, the second surface of the resin film substrate is a release surface, which typically means that an adhesive sheet having a surface (adhesive surface) of an adhesive layer provided on the first surface of the resin film substrate in contact with the release surface can be peeled off without leaving any adhesive residue (residual adhesive) on the release surface.

[0078] In some embodiments, the resin composition constituting the second surface (hereinafter also referred to as "second surface forming material") preferably contains a release agent. A resin film substrate having such a second surface can be understood as a resin film substrate having the release agent kneaded into at least the second surface. The second surface forming material only needs to constitute at least the second surface of the resin film substrate, and may, for example, constitute only the second surface side of the resin film substrate, or may constitute the entire resin film substrate.

[0079] The second surface forming material can preferably be a resin composition containing at least a release agent and a resin material. The resin material can be, but is not limited to, various materials exemplified as the resin material constituting the resin film substrate, such as polyester resins such as PET and PBT; polyolefin resins such as PE, PP, ethylene-propylene copolymers, and PP-PE blend resins; and other vinyl chloride resins (typically soft vinyl chloride resins), vinyl acetate resins, and polyamide resins.

[0080] Examples of release agents that can be used as a component of the second surface forming material (i.e., release agents for kneading into the second surface) include ethylene-vinyl alcohol copolymers, fatty acid amide additives, low molecular weight polyolefin waxes, long chain alkyl additives, silicone release agents, etc. The release agents can be used alone or in appropriate combination of two or more. It is preferable to select a release agent that has good mixability with the resin component contained in the second surface forming material.

[0081] As the ethylene-vinyl alcohol copolymer, for example, an ethylene-vinyl alcohol copolymer obtained by saponifying a copolymer of ethylene with vinyl acetate, vinyl formate, vinyl propionate, or vinyl acetate can be used. Examples of fatty acid amide additives include saturated fatty acid bisamides, unsaturated fatty acid bisamides, aromatic bisamides, and substituted ureas. More specifically, examples of fatty acid amide additives include methylene bisstearic acid amide, ethylene bisstearic acid amide, ethylene bisoleic acid amide, N,N-dioleyl adipic acid amide, N-stearyl-N'-stearyl urea, and other N-stearyl-N'-stearyl acid amides. These fatty acid amide additives may be used alone or in combination of two or more. As the low molecular weight polyolefin wax, for example, low molecular weight waxes such as polyethylene wax and polypropylene wax can be appropriately used. As the long-chain alkyl additive, low molecular weight additives having an alkyl chain, such as Peloil (registered trademark) 1010 and Peloil (registered trademark) 1010S (both manufactured by Ipposha Yushi Kogyo Co., Ltd.), can be appropriately used. Examples of silicone-based release agents include silylated polyolefins, silicone resins, silicone alkoxy oligomers, silicone oligomers, silicone master pellets, silicone rubber powders, silicone emulsions, etc. As the silylated polyolefins, for example, silylated polyolefins prepared by the method shown in the examples of JP-A-2011-26448 can be used.

[0082] Suitable examples of the release agent for kneading on the second surface include the above-mentioned long-chain alkyl additives and silicone-based release agents. Among them, silicone-based release agents are particularly preferred. As the silicone-based release agent, silylated polyolefin is particularly preferred.

[0083] The content of the release agent in the second-surface forming material is not particularly limited, and may be, for example, about 0.01 to 80% by weight of the entire second-surface forming material. In some embodiments, the content of the release agent in the second-surface forming material may be, for example, 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, 0.7% by weight or more, or 1% by weight or more. From the viewpoint of compatibility with the resin material, etc., the content of the release agent in the second-surface forming material may be, for example, 70% by weight or less, 50% by weight or less, 30% by weight or less, or 10% by weight or less.

[0084] The resin film substrate may be a single layer structure or a multi-layer structure of two or more layers. In some embodiments, a resin film substrate with a multi-layer structure may be preferably used. A resin film substrate with a multi-layer structure has an advantage that the function and appearance of the first surface and the second surface of the resin film substrate can be easily made different. In a resin film substrate with a multi-layer structure, the types of resin materials constituting each layer may be the same or different. The resin film substrate with a multi-layer structure may be, for example, a 2-layer to 5-layer structure, or may be a 2-layer or 3-layer structure. In some other embodiments, the resin film substrate may be a single layer structure. A resin film substrate with a single layer structure may be advantageous in terms of the productivity and quality stability of the resin film substrate.

[0085] The molding method of the resin film substrate is not particularly limited, and a conventionally known extrusion molding method, such as an inflation extrusion molding method or a cast molding method, can be appropriately adopted. The resin film substrate may be unstretched, or may be stretched uniaxially or biaxially. A multi-layered resin film substrate can be obtained by using a method of simultaneously molding resin compositions corresponding to each layer (for example, by a multi-layer inflation molding method), a method of laminating each layer after molding, a method of casting another layer on a layer previously molded, or the like, either alone or in combination.

[0086] In the pressure-sensitive adhesive sheet disclosed herein, the method of forming the second surface as a release surface may preferably be a method of forming the second surface of the resin film substrate with a second surface forming material containing a release agent in a resin composition as described above, but is not limited thereto. The second surface of the resin film substrate may be a release surface obtained by, for example, applying a release agent to a surface formed of a resin composition not containing a release agent. Such a surface treatment may be carried out using, for example, a general silicone-based, long-chain alkyl-based, fluorine-based or other release agent. The surface formed of a resin composition containing a release agent (i.e., the surface into which the release agent is kneaded) may be further subjected to a surface treatment of applying a release agent.

[0087] The resin film substrate may contain a laser beam absorbent as necessary. In some embodiments, the laser beam absorbent preferably contains a specific absorbent described below. A suitable example of a resin film substrate containing a laser beam absorbent is a resin film substrate containing a laser beam absorbing layer (which may be a specific absorbent). In a multi-layered resin film substrate, at least one layer is preferably a laser beam absorbing layer containing a laser beam absorbent.

[0088] The laser light absorptivity of the resin film substrate including the laser light absorbing layer is not particularly limited, but can be set so that the laser light absorptivity of the adhesive sheet is 20% or more. In some embodiments, the laser light absorptivity of the resin film substrate may be, for example, 15% or more, and usually 20% or more is appropriate, and may be 25% or more, 30% or more, 45% or more, 60% or more, or 75% or more. The laser light absorptivity of the resin film substrate may be 100%, but in practical terms, it is preferably 95% or less, and may be 90% or less. In addition, the transmittance and reflectance of the resin film substrate may be appropriately selected from the same range as the transmittance and reflectance of the adhesive sheet described below.

[0089] The laser beam absorbent contained in the resin film substrate may be one type alone or two or more types in combination selected from the laser beam absorbents exemplified below as usable in the pressure-sensitive adhesive sheet. In an embodiment in which the laser beam absorbent contains a specific absorbent, the specific absorbent may be one type alone or two or more types in combination selected from the laser beam absorbents exemplified below as usable in the pressure-sensitive adhesive sheet. The content of the laser beam absorbent and the content of the specific absorbent in the resin film substrate may be within the ranges exemplified below as the content of the laser beam absorbent and the content of the specific absorbent in the pressure-sensitive adhesive sheet.

[0090] Any additives may be added to the resin film substrate as necessary, such as flame retardants, antistatic agents, light stabilizers (radical scavengers, ultraviolet absorbers, etc.), and antioxidants.

[0091] The thickness of the resin film substrate is not particularly limited, and can be, for example, about 5 μm to 300 μm. From the viewpoint of the handleability of the resin film substrate or the adhesive sheet having the resin film substrate, in some preferred embodiments, the thickness of the resin film substrate may be, for example, 15 μm or more, 20 μm or more, 35 μm or more, 50 μm or more, or 75 μm or more. According to an adhesive sheet having a resin film substrate having a predetermined thickness, for example, sufficient protection is easily obtained in the surface protection application of an adherend. In addition, in some preferred embodiments, the thickness of the resin film substrate is, for example, 150 μm or less, 130 μm or less, 110 μm or less, or 90 μm or less. Reducing the thickness of the resin film substrate can be advantageous from the viewpoint of making the adhesive sheet thinner. In addition, when the thickness of the resin film substrate is reduced, the flexibility of the adhesive sheet and its ability to follow the surface shape of the adherend tend to improve. In addition, when applied to laser processing applications, the speed and precision of laser processing can be improved by limiting the thickness of the resin film substrate. In some other embodiments, the thickness of the resin film substrate may be 70 μm or less, 50 μm or less, or 40 μm or less.

[0092] In a resin film substrate containing a laser light absorbing layer, the thickness of the laser light absorbing layer (in a resin film substrate containing a plurality of laser light absorbing layers, the total thickness of those layers) may be, for example, 3 μm or more, 5 μm or more, or 10 μm or more. From the viewpoint of the speed and precision of laser processing, in some embodiments, the thickness of the laser light absorbing layer (in other words, the portion where the laser light absorbent is disposed) of the entire thickness of the resin film substrate may be, for example, 20% or more, 50% or more, 70% or more, or 90% or more. In a single-layer resin film substrate consisting of a laser light absorbing layer or a resin film substrate consisting of a plurality of laser light absorbent layers, the thickness of the laser light absorbing layer is 100% of the entire thickness of the substrate.

[0093] <Undercoat layer> The pressure-sensitive adhesive sheet includes an undercoat layer disposed on the surface of the resin film substrate facing the pressure-sensitive adhesive layer. The undercoat layer is formed from an undercoat agent containing a water-dispersible polymer having an oxazoline group (a water-dispersible polymer containing an oxazoline group). By disposing the undercoat layer between the resin film substrate and the pressure-sensitive adhesive layer, the anchoring property of the pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive composition containing the rubber latex (A) and the aqueous crosslinking agent (C) can be effectively improved without relying on an organic solvent-containing material. In addition, the adhesive residue prevention property can also be improved. Furthermore, by using a water-dispersible polymer as the undercoat agent, the undercoat layer can exhibit good water resistance and desired performance with respect to the rubber-based latex-containing pressure-sensitive adhesive composition. In addition, the use of a water-dispersible polymer is preferable because it has less effect on the adhesive properties of the pressure-sensitive adhesive layer provided on the undercoat layer than a water-soluble polymer. The water-dispersible polymer refers to a polymer that exhibits dispersibility in water. As the water-dispersible polymer containing an oxazoline group, a polymer emulsion containing an oxazoline group is typically used.

[0094] As the oxazoline group-containing water-dispersible polymer, for example, an acrylic polymer or a urethane polymer containing an oxazoline group in the side chain can be used. Among them, the use of an acrylic polymer having an oxazoline group is particularly preferred. A monomer such as styrene may be copolymerized in the main chain of the acrylic polymer having an oxazoline group.

[0095] The glass transition temperature (Tg) of the oxazoline group-containing water-dispersed polymer is not particularly limited. In some embodiments, the Tg of the oxazoline group-containing water-dispersed polymer may be about 50°C or less, about 30°C or less, or about 10°C or less. In some preferred embodiments, from the viewpoint of improving the anchoring property of the adhesive layer, the Tg is preferably about 0°C or less, more preferably about -20°C or less, even more preferably about -30°C or less, and even more preferably about -40°C or less. According to the oxazoline group-containing water-dispersed polymer having a low Tg, the undercoat agent is easily applied to the resin film (e.g., polyolefin resin film), and the film-forming property tends to be good. In some embodiments, the lower limit of the Tg of the oxazoline group-containing water-dispersed polymer is, for example, about -80°C or more, may be about -70°C or more, or may be about -60°C or more. For the Tg of the polymer, the manufacturer's nominal value may be adopted for commercially available products. When the manufacturer's nominal value is unknown or for polymers obtained by synthesis, analysis can be performed using a differential scanning calorimeter (DSC) to confirm the Tg of the synthetic rubber from the temperature of the inflection point of the obtained heat curve. As a DSC, a TA Instruments product name "Q2000" or an equivalent product can be used.

[0096] Although not particularly limited, in some embodiments, the proportion of the oxazoline group-containing water-dispersible polymer in the undercoat layer is, for example, approximately 50% by weight or more (e.g., more than 50% by weight) based on the non-volatile content, may be approximately 70% by weight or more, may be approximately 90% by weight or more, or may be approximately 95% by weight or more, and the undercoat layer may be substantially composed of the oxazoline group-containing water-dispersible polymer.

[0097] The undercoat agent may contain various additives, such as surfactants, thickeners, stabilizers, defoamers, colorants (pigments, dyes, etc.), etc., as necessary.

[0098] Commercially available undercoat agents used for forming the undercoat layer include those available under the trade names "Epocross K-2010E", "Epocross K-2020E" and "Epocross K-2035E" manufactured by Nippon Shokubai Co., Ltd.

[0099] The undercoat agent can be formed by directly applying the undercoat agent to the surface of the resin film substrate using an applicator such as a wire bar, a spray coater, a fountain die coater, a lip coater, a closed edge die coater, a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, etc., and then drying the undercoat agent. The undercoat layer is typically formed continuously, but is not limited thereto, and may be formed in a regular or random pattern such as a dotted or striped pattern.

[0100] The thickness of the undercoat layer (after drying) is not particularly limited. In some embodiments, the thickness of the undercoat layer may be 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, 0.5 μm or more, or 1.0 μm or more. In some preferred embodiments, the thickness of the undercoat layer is 3 μm or less, 2 μm or less, or 1.5 μm or less. By setting the thickness of the undercoat layer within the above range, the anchoring force improvement effect due to the arrangement of the undercoat layer can be preferably exhibited.

[0101] (Laser Light Absorbing Agent and Laser Light Absorbing Layer) In some embodiments, the adhesive sheet contains a laser beam absorbent. The laser beam absorbent can be used to adjust the laser beam absorptivity of the adhesive sheet. As the laser beam absorbent, various materials that can increase the absorptivity of the laser beam used in processing (typically, at least the absorptivity at the main wavelength) can be preferably used. The type of laser beam absorbent contained in the adhesive sheet may be one type, or two or more types. In an adhesive sheet containing two or more types of laser beam absorbents, the laser beam absorbents may be used in a blend, or may be contained in different layers in the adhesive sheet.

[0102] In this specification, the term "laser beam absorbent" refers to a material that can increase the laser beam absorption rate compared to when the laser beam absorbent is not used. In addition, in this specification, the term "specific absorbing agent" refers to the above-mentioned laser beam absorbents that have as a constituent element a metal with a specific heat of less than 900 J / kg·K and a thermal conductivity of less than 200 W / m·K. In this specification, a layer containing a laser beam absorbent (which may be a specific absorbing agent) may be referred to as a "laser beam absorbing layer."

[0103] Examples of the laser light absorbent that can be used in the adhesive sheet disclosed herein include metals such as aluminum, stainless steel, titanium, nickel, zirconium, tungsten, copper, silver, gold, zinc, molybdenum, chromium, and alloys mainly composed of these metals; metal compounds such as oxides (e.g., titanium oxide, aluminum oxide, etc.), nitrides, and carbides of the above metals; carbon materials such as carbon black and carbon fiber; organic compounds such as phthalocyanine compounds, cyanine compounds, aminium compounds, naphthalocyanine compounds, naphthoquinone compounds, diimonium compounds, anthraquinone compounds, and aromatic dithiol metal complexes (e.g., nickel complexes); and the like. In the laser light absorbing layer containing a laser light absorbent in the resin composition, it is preferable to use a material having a higher thermal decomposition temperature than the resin components constituting the laser light absorbing layer as the laser light absorbent.

[0104] When a powdered laser beam absorbent is used, the shape of the particles constituting the powder is not particularly limited, and may be, for example, flaky, spherical, needle-like, polyhedral, irregular, etc. Usually, a flaky, spherical, or needle-like laser beam absorbent may be preferably used. The average particle size of the laser beam absorbent is not particularly limited, and may be, for example, 0.005 μm or more and 20 μm or less. From the viewpoint of dispersibility, usually, a laser beam absorbent having an average particle size of 10 μm or less or 5 μm or less may be preferably used. From the viewpoint of efficiently increasing the laser beam absorption rate with a small amount of laser beam absorbent, in some embodiments, the average particle size of the laser beam absorbent may be, for example, 3 μm or less, 1 μm or less, 0.6 μm or less, 0.4 μm or less, or 0.3 μm or less. From the viewpoint of powder handling and ease of uniform dispersion, in some embodiments, the average particle size of the laser beam absorbent may be, for example, 0.008 μm or more, 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, 0.15 μm or more, or 0.2 μm or more. In this specification, unless otherwise specified, the term "average particle size" refers to the particle size at an integrated value of 50% in a particle size distribution measured with a particle size distribution measuring device based on a laser scattering / diffraction method (50% volume average particle size).

[0105] In some embodiments, the laser light absorbing layer may contain carbon black as the laser light absorbing agent. For example, carbon black having an average particle size of 10 nm to 500 nm (more preferably 10 nm to 120 nm) may be used. Carbon black may be used alone or in combination with other laser light absorbing agents.

[0106] In some embodiments, the laser light absorbing layer may contain at least one of a metal powder and a metal compound powder as a laser light absorbent. Such a laser light absorbent is preferable because it can withstand heat generation accompanying absorption of a specific laser light and appropriately maintain the property of absorbing the specific laser light. Suitable examples of this type of laser light absorbent include titanium oxide powder, aluminum oxide powder, and metallic aluminum powder.

[0107] The laser light absorbing layer is typically a layer containing a laser light absorbing agent in a resin component. Non-limiting examples of materials that can be used as such a resin component include polyester resins such as PET and PBT; polyolefin resins such as PE, PP, ethylene-propylene copolymers, and PP-PE blend resins; and other vinyl chloride resins, vinyl acetate resins, and polyamide resins. The laser light absorbing layer can be formed by molding a resin composition obtained by blending a laser light absorbing agent with such a resin material into a typically film-like shape.

[0108] When using a laser beam absorbent, its amount is not particularly limited.In some embodiments, the amount of the laser beam absorbent may be, for example, 0.01% by weight or more of the laser beam absorption layer containing the laser beam absorbent, 0.05% by weight or more, or 0.1% by weight or more.In addition, from the viewpoint of reducing laser cutting residue and suppressing reflectance, in some embodiments, the content of the laser beam absorbent may be, for example, 10% by weight or less of the laser beam absorption layer containing the laser beam absorbent, 5% by weight or less, 3% by weight or less, or 2% by weight or less.

[0109] In some embodiments, the pressure-sensitive adhesive sheet disclosed herein may preferably use, as the laser beam absorbent, a specific absorbent, i.e., a laser beam absorbent having as a constituent element a metal with a specific heat of less than 900 J / kg·K and a thermal conductivity of less than 200 W / m·K. The specific absorbent may be selected from the group consisting of any one metal simple substance that satisfies the above specific heat and thermal conductivity; an alloy containing any one metal that satisfies the above specific heat and thermal conductivity at a ratio of more than 50 wt%, more than 70 wt%, or more than 90 wt%; an alloy containing two or more metals that satisfy the above specific heat and thermal conductivity at a ratio of more than 50 wt%, more than 70 wt%, or more than 90 wt% in total; a metal compound containing a metal corresponding to such a simple metal or alloy as a constituent element; and the like. The specific absorbent here includes, for example, iron, iron alloys (for example, iron alloys containing at least one element selected from the group consisting of Cr, Ni, Si, W, Mn, and C), and metal compounds (iron-based compounds) containing a metal (iron-based metal) corresponding to the iron or iron alloy as a constituent element. As the iron-based compound, for example, an oxide of the iron-based metal (iron-based oxide) can be preferably used. Other examples of the specific absorbent include Mn-based compounds containing a metal (Mn-based metal) corresponding to Mn or an Mn alloy as a constituent element, and among them, Mn-based oxides are preferred. The specific absorbent can be used alone or in combination of two or more. In a pressure-sensitive adhesive sheet containing two or more types of specific absorbents, the specific absorbents may be used in a blend, or may be contained in different layers within the pressure-sensitive adhesive sheet.

[0110] In general, the specific heat and thermal conductivity of a metal compound containing a metal as a constituent element tend to be smaller than those of a metal alone. Therefore, in some embodiments of the pressure-sensitive adhesive sheet disclosed herein, a metal compound containing a metal as a constituent element that satisfies the preferred specific heat and thermal conductivity disclosed herein can be preferably used as a specific absorbent. The metal compound that can be used as a specific absorbent can be, for example, an oxide, sulfide, carbide, nitride, hydroxide, oxyhydroxide, etc. of a metal that satisfies the preferred specific heat and thermal conductivity disclosed herein. Other examples of metal compounds that can be used as specific absorbents include metal organic compounds (complexes, etc.) that contain ions of the metal. From the viewpoint of enduring the heat generation accompanying the absorption of specific laser light and appropriately maintaining the property of absorbing the specific laser light, the oxide, sulfide, carbide, and nitride of the above metal are preferred, and oxides are particularly preferred. Examples of the oxides include iron oxide (FeO, Fe3O4, Fe2O3, etc.), manganese dioxide, titanium black, chromium oxide (CrO, Cr2O3, etc.), ferrite, etc., and examples of the sulfides include iron sulfide, molybdenum sulfide, etc., but are not limited to these.

[0111] In the case where the pressure-sensitive adhesive sheet disclosed herein contains a specific absorbent, the content of the specific absorbent is not particularly limited, and may be appropriately selected, for example, from the range of 0.01% by weight or more and 20% by weight or less of the pressure-sensitive adhesive sheet. In some embodiments, the content of the specific absorbent may be, for example, 0.05% by weight or more, 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, or 0.8% by weight or more. When the content of the specific absorbent is high, the absorption rate of the specific laser light tends to be high. On the other hand, when the content of the specific absorbent is too high, the energy of the absorbed specific laser light tends to diffuse in the surface direction, and energy loss may increase. From this viewpoint, the content of the specific absorbent is usually appropriate to be 15% by weight or less of the pressure-sensitive adhesive sheet, preferably 10% by weight or less, more preferably 7% by weight or less, and may be 5% by weight or less or less than 5% by weight.

[0112] The adhesive sheet disclosed herein may contain, in addition to the specific absorbent, a laser light absorbent other than the specific absorbent as needed. Hereinafter, the laser light absorbent other than the specific absorbent used as an auxiliary in this way is also referred to as an "auxiliary absorbent". The auxiliary absorbent may be used for the purpose of, for example, improving the absorption rate of the adhesive sheet, adjusting the transmittance or reflectance, adjusting the appearance, etc. Examples of the auxiliary absorbent include metals such as aluminum, copper, silver, and gold; metal compounds such as oxides, nitrides, and carbides of the above metals; carbon black; organic compounds such as phthalocyanine compounds, cyanine compounds, aminium compounds, naphthalocyanine compounds, naphthoquinone compounds, diimonium compounds, and anthraquinone compounds; and the like.

[0113] The amount of auxiliary absorbent used is preferably less than 50% by weight of the total amount of laser light absorbent contained in the adhesive sheet (i.e., the total amount of the specific absorbent and the auxiliary absorbent), and may be less than 25%, less than 10%, or less than 5%. The adhesive sheet may be substantially free of auxiliary absorbent. Here, substantially free of auxiliary absorbent means that the auxiliary absorbent is not used at least intentionally. The total amount of laser light absorbent contained in the adhesive sheet is suitably 25% by weight or less of the adhesive sheet, and more preferably 20% by weight or less, 15% by weight or less, or 10% by weight or less.

[0114] When the adhesive sheet disclosed herein contains a specific absorbent, the carbon black (CB) content of the adhesive sheet is preferably less than 0.3% by weight of the adhesive sheet, more preferably less than 0.1% by weight, even more preferably less than 0.05% by weight, and particularly preferably 0.02% by weight or less. The reduction in the CB content tends to improve the non-contamination properties of the adhesive sheet. The adhesive sheet may be substantially free of CB, that is, an adhesive sheet in which CB is not used at least intentionally. The adhesive sheet disclosed herein contains a specific absorbent, so that the workpiece can be efficiently processed even if no CB is used or the amount of CB used is limited as described above. With such an adhesive sheet, the improvement in the processing efficiency of the workpiece and the non-contamination properties can be suitably achieved at the same time.

[0115] In some embodiments, a black metal compound may be preferably used as the specific absorbent. The use of a black metal compound can efficiently increase the laser light absorptivity of the adhesive sheet. This makes it possible to preferably realize an adhesive sheet having the above-mentioned preferred laser light absorptivity even if CB is not used or the amount of CB used is limited. The inventors' study has revealed that, unexpectedly, unlike CB, such black metal compounds are less likely to produce black residues. Therefore, the use of a black metal compound can preferably achieve both improved processing efficiency and non-contamination of the workpiece.

[0116] Examples of black metal compounds include, but are not limited to, iron oxide, manganese dioxide, titanium black, chromium oxide, iron sulfide, molybdenum sulfide, etc. In terms of availability, preferred black metal compounds include iron oxide (e.g., FeO, Fe3O4, etc.), titanium black, manganese dioxide, etc. The titanium black is black particles having titanium atoms, and is preferably black particles such as titanium oxynitride and low-order titanium oxide. Among these, preferred black metal compounds include iron oxide and titanium black.

[0117] The content of the black metal compound in the adhesive sheet can be, for example, 0.05% by weight or more of the adhesive sheet, and from the viewpoint of improving the laser light absorption rate, it may be 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, or 0.8% by weight or more. In addition, from the viewpoint of reducing the energy loss due to diffusion in the surface direction of the adhesive sheet, the content of the black metal compound is usually appropriate to be 15% by weight or less of the adhesive sheet, preferably 10% by weight or less, more preferably 7% by weight or less, and may be 5% by weight or less or less than 5% by weight. Alternatively, the proportion of the black metal compound in the specific absorbent may be, for example, more than 50% by weight, may be 70% by weight or more, may be 90% by weight or more, or may be substantially 100% by weight.

[0118] (Adhesive sheet thickness) The thickness of the adhesive sheet is not particularly limited, and is usually about 10 μm to 500 μm. From the viewpoint of the handleability of the adhesive sheet, in some embodiments, the thickness of the adhesive sheet may be, for example, 20 μm or more, 25 μm or more, 40 μm or more, 55 μm or more, 70 μm or more, or 80 μm or more. In some embodiments, the thickness of the adhesive sheet may be, for example, 300 μm or less, 150 μm or less, 120 μm or less, or 100 μm or less. An adhesive sheet having the above thickness can be preferably used for surface protection applications. In addition, when the adhesive sheet is applied to laser processing applications, the speed and precision of the laser processing can be improved by limiting the thickness of the adhesive sheet. In other embodiments, the thickness of the adhesive sheet may be 80 μm or less, 60 μm or less, or 50 μm or less. An adhesive sheet having a reduced thickness as described above can be preferably used for applications in which thinning and weight reduction are desired.

[0119] <Characteristics of adhesive sheet> Although not particularly limited, in an embodiment in which the adhesive sheet is used for laser processing, the adhesive sheet preferably has a laser light absorptance in the wavelength range of the laser light used for processing (typically, the laser light absorptance at the main wavelength of the laser light) of 20% or more. This laser light absorptance means the proportion of the laser light actually absorbed by the adhesive sheet out of the laser light irradiated to the adhesive sheet. According to an adhesive sheet having a laser light absorptance of 20% or more, the laser light can be efficiently absorbed. In some embodiments, the laser light absorptance of the adhesive sheet may be, for example, 25% or more, 30% or more, 45% or more, 60% or more, or 75% or more. The laser light absorptance of the adhesive sheet may be 100%, but in practical terms, it is preferably 95% or less, and may be 90% or less.

[0120] In this specification, the term "laser light absorptance" refers to a value calculated from the transmittance T (%) and reflectance R (%) of a sample measured using a spectrophotometer (e.g., a spectrophotometer manufactured by Hitachi High-Technologies Corporation, model "U-4100" or an equivalent product) using the following formula (I). Absorption rate A(%)=100(%)-T(%)-R(%) (I)

[0121] In this specification, for example, "laser light absorptance in the wavelength range of 900 nm to 1100 nm" refers to the minimum laser light absorptance in that wavelength range. Furthermore, unless otherwise specified, the laser light absorptance in this specification refers to the laser light absorptance of the back surface of the adhesive sheet or substrate (the surface on the side irradiated with the laser light, i.e., the surface opposite to the surface attached to the workpiece).

[0122] The transmittance and reflectance of the adhesive sheet are not particularly limited. In some embodiments, the adhesive sheet may have a laser light transmittance of less than 70% at a wavelength where the laser light absorptance is the minimum within the wavelength range of the laser light used for processing, for example, less than 50%. In some embodiments, the adhesive sheet may have a laser light reflectance of less than 50% at a wavelength where the laser light absorptance is the minimum, for example, less than 40%, less than 20%, or less than 10%. An adhesive sheet that satisfies at least one of the transmittance and the reflectance (preferably both) is likely to have the preferred laser light absorptance disclosed herein.

[0123] <Application> The use of the adhesive sheet disclosed herein is not particularly limited. It can be applied to various applications in which an adhesive sheet having a resin film substrate can be used, and can contribute to reducing the amount of organic solvent used in such applications. The adhesive sheet disclosed herein can be used, for example, for the purpose of fixing or joining components in various parts or products (for example, for the purpose of performing the fixing or joining semi-permanently). In addition, the adhesive sheet disclosed herein has good anchoring properties of the adhesive layer to the resin film substrate, so that adhesive residue is unlikely to occur when peeled off from the adherend. Therefore, it is suitable as an adhesive sheet for surface protection that is attached to the surface of an adherend and peeled off from the adherend after achieving its protective purpose. For example, it can be used for applications such as attaching to the surface of components such as metal plates, painted plates, aluminum sashes, resin plates, decorative steel plates, vinyl chloride laminated steel plates, glass plates, optical films for liquid crystal such as polarizing films, optical components such as liquid crystal panels, electronic components, etc., when transporting, processing, or curing these components. In addition, the adhesive sheet disclosed herein is also suitable as a packaging adhesive sheet. Adhesive sheets used for packaging textiles, paper, boxes, and other packaging materials are required to be removed smoothly without leaving any adhesive residue when the package is opened. The adhesive sheets disclosed herein can be preferably used for such applications.

[0124] The adhesive sheet disclosed herein can be preferably used as one aspect of surface protection in a state where it is attached to a workpiece to be processed by various lasers and is laser cut in association with the laser processing of the workpiece. The laser light used in the above-mentioned laser processing is not particularly limited, and various conventionally known lasers can be adopted. For example, excimer lasers such as ArF excimer laser, KrF excimer laser, and XeCl excimer laser, solid-state lasers such as YAG laser, YLF laser, YVO4 laser, and titanium sapphire laser, semiconductor laser (sometimes called diode laser), fiber laser, carbon dioxide laser, etc. can be used. The type of laser processing performed on the workpiece with the adhesive sheet disclosed herein attached is not particularly limited, and can be, for example, cutting, drilling, cutting, engraving, etc.

[0125] The material of the workpiece is not particularly limited as long as it can be cut by laser light (for example, laser light of a carbon dioxide gas laser or a fiber laser), and may be, for example, metal or semimetal materials such as iron, iron alloys (carbon steel, stainless steel, chromium steel, nickel steel, etc.), aluminum, aluminum alloys, nickel, tungsten, copper, copper alloys, titanium, titanium alloys, silicon, etc.; resin materials such as polyolefin resins, polycarbonate resins, acrylic resins, etc.; ceramic materials such as alumina, silica, sapphire, silicon nitride, tantalum nitride, titanium carbide, silicon carbide, gallium nitride, gypsum, etc.; glass materials such as aluminosilicate glass, soda lime glass, soda aluminosilicate glass, quartz glass, etc.; cellulose-based materials such as paper, cardboard, wood, plywood, etc.; laminates or composites thereof; etc. Suitable examples of the workpiece include metal materials such as iron, aluminum, copper, titanium, and alloys (stainless steel, etc.) mainly composed of each of these metals. The shape of the workpiece is not particularly limited, and may be plate-shaped, cylindrical, block-shaped, etc. The adhesive sheet disclosed herein is preferable because it suppresses lateral slippage even when attached to a metal plate as a workpiece and then stacked.

[0126] The adhesive sheet disclosed herein can be preferably used in such laser processing in a state where it is attached to the surface of the workpiece on the laser light irradiation side. In addition, for the purpose of protecting the surface of the workpiece before and after laser processing or during laser processing, the adhesive sheet may be attached to the surface (back side) of the workpiece opposite to the laser light irradiation side. The adhesive sheet disclosed herein can be preferably used in such laser processing by a short-wavelength laser having a main wavelength of 900 to 1100 nm. As the short-wavelength laser, for example, a fiber laser having a main wavelength of about 1050 nm, a diode laser having a main wavelength of about 950 nm, etc. can be used.

[0127] The matters disclosed in this specification include the following. [1] A pressure-sensitive adhesive sheet having a resin film substrate, an undercoat layer, and a pressure-sensitive adhesive layer in this order, the pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition containing a rubber-based latex and an aqueous crosslinking agent, The pressure-sensitive adhesive sheet, wherein the undercoat layer contains a water-dispersible polymer having an oxazoline group. [2] A pressure-sensitive adhesive sheet having a resin film substrate, an undercoat layer, and a pressure-sensitive adhesive layer in this order, the undercoat layer is provided on at least one surface of the resin film substrate and is in contact with the pressure-sensitive adhesive layer; the pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition containing a rubber-based latex and an aqueous crosslinking agent, The aqueous crosslinking agent includes an aqueous crosslinking agent having at least one functional group selected from an oxazoline group, an isocyanate group, and an epoxy group, The pressure-sensitive adhesive sheet, wherein the undercoat layer contains a water-dispersible polymer having an oxazoline group. [3] The pressure-sensitive adhesive sheet according to the above-mentioned [1] or [2], wherein the resin film substrate is a polyolefin-based resin film substrate. [4] The pressure-sensitive adhesive sheet according to any one of the above [1] to [3], wherein the water-dispersible polymer having an oxazoline group has a glass transition temperature of 0° C. or lower. [5] The pressure-sensitive adhesive sheet according to any one of [1] to [4] above, wherein the content of the aqueous crosslinking agent in the pressure-sensitive adhesive layer is 0.1 parts by weight or more per 100 parts by weight of the rubber latex, based on the non-volatile content. [6] The pressure-sensitive adhesive sheet according to any one of the above [1] to [5], wherein the undercoat layer has a thickness of 0.01 μm or more and 3 μm or less. [7] The pressure-sensitive adhesive sheet according to any one of the above [1] to [6], wherein the rubber-based latex contains natural rubber latex in a proportion of 50% by weight or more based on the non-volatile content. [8] The pressure-sensitive adhesive sheet according to any one of the above [1] to [7], which is used for protecting the surface of an adherend. EXAMPLES

[0128] Some examples of the present invention will be described below, but it is not intended that the present invention be limited to those specific examples. In the following description, "parts" and "%" are by weight unless otherwise specified.

[0129] <Preparation of tackifier resin emulsion> A resin solution was obtained by dissolving 100 parts of an aliphatic hydrocarbon resin (manufactured by ENEOS, product name "T-REZ RB100", softening point 100°C) in 40 parts of toluene. In addition, 4 parts of casein, 60 parts of water, and 28% ammonia water were mixed, and the casein was heated and dissolved at 70°C to obtain an aqueous ammonia solution of casein. The amount of 28% ammonia water used was 15 parts per 100 parts of casein. The aqueous ammonia solution of casein was cooled to 40°C, and 8 parts of ammonium salt of hydrogenated rosin (60% dihydroabietic acid) was added and mixed as an emulsifier to obtain an emulsifier-containing liquid. The emulsifier-containing liquid was then mixed with the resin solution, and the mixture was stirred at 800 rpm for 1 hour using a T·K homodisper manufactured by Tokushu Kika Kogyo Co., Ltd. to prepare a tackifier resin emulsion. The temperature of the emulsifier-containing liquid and the resin solution was adjusted to 40°C to prepare the tackifier resin emulsion.

[0130] <Example 1> (Preparation of Pressure-Sensitive Adhesive Composition) To 100 parts of natural rubber latex (available from Nomura Trading Co., Ltd., trade name "HYTEX HA", hereinafter sometimes referred to as "NR") on a non-volatile basis, 70 parts of the tackifier resin emulsion obtained above, 2 parts of an antioxidant (manufactured by Seiko Chemical Co., Ltd., trade name "Nonflex CBP-E"), and 1 part of a water-soluble oxazoline-based crosslinking agent (manufactured by Nippon Shokubai Co., Ltd., trade name "Epocross WS-700") were added and mixed to prepare a water-dispersible pressure-sensitive adhesive composition according to this example.

[0131] (Preparation of adhesive sheet) An oxazoline group-containing polymer emulsion (product name "Epocross K-2010E" by Nippon Shokubai Co., Ltd., Tg-50°C) was applied with wire bar #3 to the first surface of a polyethylene film (manufactured by Okura Kogyo Co., Ltd., product name "SHO Film", thickness 50 μm) used as a resin film substrate, and then dried to form an undercoat layer (application amount: 1.4 g / m2 based on non-volatile content). 2 ). The pressure-sensitive adhesive composition was applied to the surface of the undercoat layer of the resin film substrate and dried to form a pressure-sensitive adhesive layer having a thickness of 12 μm. In this manner, a pressure-sensitive adhesive sheet having an undercoat layer on the first surface of the resin film substrate and an adhesive layer on the undercoat layer was obtained.

[0132] <Example 2> In the preparation of the adhesive composition of Example 1, a water-dispersible isocyanate crosslinking agent (manufactured by DIC Corporation, product name "Burnoc DNW-6000") was used instead of the water-soluble oxazoline crosslinking agent. Otherwise, an adhesive sheet according to this example was obtained in the same manner as in Example 1.

[0133] <Example 3> In the preparation of the adhesive composition of Example 1, 90 parts of the above natural rubber latex and 10 parts of acid-modified SBR latex (manufactured by Nippon Zeon Co., Ltd., product name "Nipol LX432M", Tg-55°C, hereinafter sometimes referred to as "SBR") were used instead of 100 parts of natural rubber latex, based on non-volatile content. Otherwise, an adhesive sheet according to this example was obtained in the same manner as in Example 1.

[0134] <Examples 4-5> In the preparation of the pressure-sensitive adhesive composition of Example 3, the amount of the water-soluble oxazoline crosslinking agent was changed to 0.5 parts (Example 4) or 5 parts (Example 5) based on the non-volatile content per 100 parts of the total amount of the rubber latex. Otherwise, pressure-sensitive adhesive sheets according to each example were obtained in the same manner as in Example 3.

[0135] <Example 6> In the preparation of the adhesive composition of Example 3, a water-soluble epoxy-based crosslinking agent (manufactured by Nagase ChemteX Corporation, product name "Denacol EX-313") was used instead of the water-soluble oxazoline-based crosslinking agent. Otherwise, an adhesive sheet according to this example was obtained in the same manner as in Example 3.

[0136] <Example 7> An oxazoline group-containing polymer emulsion (product name "Epocross K-2020E" by Nippon Shokubai Co., Ltd., Tg 0°C) was applied with wire bar #3 to the first surface of a polyethylene film (manufactured by Okura Kogyo Co., Ltd., product name "SHO Film", thickness 50 μm) used as a resin film substrate, and then dried to form an undercoat layer (application amount: 1.4 g / m2 based on non-volatile content). 2 A pressure-sensitive adhesive sheet according to this example was obtained in the same manner as in Example 2, except that this resin film substrate with an undercoat layer was used.

[0137] <Example 8> Based on the non-volatile content, 100 parts of acid-modified SBR latex (manufactured by Nippon Zeon Co., Ltd., trade name "Nipol LX432M", Tg-55°C) were mixed with 70 parts of rosin ester emulsion (manufactured by KRATON Co., Ltd., trade name "AQUATACK 6085", softening point 82°C), 2 parts of antioxidant (manufactured by Seiko Chemical Co., Ltd., trade name "Nonflex CBP-E"), and 1 part of water-soluble oxazoline crosslinking agent (manufactured by Nippon Shokubai Co., Ltd., trade name "Epocross WS-700") to prepare a water-dispersed adhesive composition according to this example. A pressure-sensitive adhesive sheet according to this example was obtained in the same manner as in Example 1, except that this pressure-sensitive adhesive composition was used.

[0138] <Example 9> In the preparation of the adhesive sheet of Example 1, the adhesive composition was applied to a first surface of a polyethylene film (manufactured by Okura Kogyo Co., Ltd., product name "SHO film", thickness 50 μm) as a resin film substrate, and dried to form an adhesive layer having a thickness of 12 μm. The adhesive sheet of this example was obtained in the same manner as in Example 1.

[0139] <Example 10> In the preparation of the adhesive sheet of Example 9, a corona discharge treatment was applied to the first surface of a polyethylene film (manufactured by Okura Kogyo Co., Ltd., product name "SHO film", thickness 50 μm) as a resin film substrate, and then an adhesive composition was applied to the corona discharge treated surface and dried to form an adhesive layer having a thickness of 12 μm. The adhesive sheet of this example was obtained in the same manner as in Example 9.

[0140] <Example 11> In producing the pressure-sensitive adhesive sheet of Example 1, a polyester emulsion (manufactured by Toyobo MC Co., Ltd., product name "Binalol MD-1100", Tg 40°C) was applied with wire bar #3 to the first surface of a polyethylene film (manufactured by Okura Kogyo Co., Ltd., product name "SHO Film", thickness 50 μm) serving as a resin film substrate, and then dried to form an undercoat layer (amount applied: 1.4 g / m2 based on non-volatile content). 2 A pressure-sensitive adhesive sheet according to this example was obtained in the same manner as in Example 2, except that this resin film substrate with an undercoat layer was used.

[0141] <Example 12> Except for not using a water-soluble oxazoline-based crosslinking agent, a pressure-sensitive adhesive composition was prepared in the same manner as in Example 1. Except for using this pressure-sensitive adhesive composition, a pressure-sensitive adhesive sheet according to this example was obtained in the same manner as in Example 1.

[0142] <Example 13> In producing the pressure-sensitive adhesive sheet of Example 1, a water-soluble oxazoline group-containing polymer (product name "Epocross WS-700", product name of Nippon Shokubai Co., Ltd., Tg 50°C) was applied with wire bar #3 to the first surface of a polyethylene film (manufactured by Okura Kogyo Co., Ltd., thickness 50 μm) used as a resin film substrate, and then dried to form an undercoat layer (amount applied: 1.4 g / m2 based on non-volatile content). 2A pressure-sensitive adhesive sheet according to this example was obtained in the same manner as in Example 1, except that this resin film substrate with an undercoat layer was used.

[0143] <Performance evaluation> The adhesive layer of the pressure-sensitive adhesive sheet prepared above was evaluated for anchoring ability by the following method. The results are shown in Table 1.

[0144] (1) Finger abrasion test The adhesive sheet was cut into a width of 20 mm and fixed to an acrylic plate so that the adhesive layer surface faced outward. A predetermined area (approximately 1 cm x 3 cm) on the adhesive layer surface was rubbed strongly with a finger with a constant force, and the number of rubs until the adhesive layer peeled off was recorded. In addition, the degree of peeling of the adhesive layer after rubbing three times was visually observed and evaluated according to the following criteria. A: No peeling of the adhesive layer was observed. B: The peeled area of ​​the adhesive layer was 10% or less. C: The peeled area of ​​the adhesive layer was more than 10% and 50% or less. D: The area of ​​the adhesive layer that was peeled off was more than 50%. In the finger abrasion test, if the peeling evaluation after rubbing three times was C or higher, it was judged as passing, and if the peeling evaluation after rubbing three times was D, it was judged as failing.

[0145] (2) Picking test The adhesive sheet was cut into pieces with a width of 20 mm, and the adhesive layer surfaces were bonded together with a hand roller. After 1 minute, the bonded adhesive layers were peeled off with a certain force. This bonding and peeling operation was repeated, and the number of picking operations until the adhesive layer peeled off was recorded. In addition, the degree of peeling of the adhesive layer after the third picking operation was visually observed and evaluated according to the following criteria. A: No peeling of the adhesive layer was observed. B: The peeled area of ​​the adhesive layer was 10% or less. C: The peeled area of ​​the adhesive layer was more than 10% and 50% or less. D: The area of ​​the adhesive layer that was peeled off was more than 50%. In the above picking test, if the peeling evaluation after the third picking operation was C or higher, it was judged as passing, and if the peeling evaluation after the third picking operation was D, it was judged as failing.

[0146] [Table 1]

[0147] As shown in Table 1, the adhesive sheets according to Examples 1 to 8 have an undercoat layer formed from an oxazoline group-containing polymer emulsion between an adhesive layer formed from an adhesive composition containing rubber latex and a resin film substrate, and the adhesive layer contains an oxazoline crosslinking agent, an isocyanate crosslinking agent, or an epoxy crosslinking agent as an aqueous crosslinking agent, and the finger abrasion test and the picking test were all pass. On the other hand, Example 9, which does not have an undercoat layer, Example 10, which was subjected to corona treatment instead of undercoat, Example 11, which used a polyester undercoat, Example 12, which did not contain a crosslinking agent in the adhesive layer, and Example 13, which used a water-soluble oxazoline group-containing polymer as an undercoat, all failed the finger abrasion test and the picking test. From the above results, it can be seen that a configuration comprising a resin film substrate, an undercoat layer, and an adhesive layer in this order, where the adhesive layer is formed from an adhesive composition containing a rubber-based latex and an aqueous crosslinking agent, where the aqueous crosslinking agent contains an aqueous crosslinking agent having at least one functional group selected from an oxazoline group, an isocyanate group, and an epoxy group, and where the undercoat layer contains a water-dispersible polymer having an oxazoline group, provides good anchoring properties without relying on organic solvents.

[0148] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Explanation of symbols]

[0149] 1 Adhesive sheet 10 Resin film substrate 10A 1st side 10B 2nd side (back, peeling surface) 20 Adhesive layer 20A surface (adhesive surface) 30 Undercoat layer 30A (undercoat layer) surface

Claims

1. A pressure-sensitive adhesive sheet having a resin film substrate, an undercoat layer, and a pressure-sensitive adhesive layer in this order, the undercoat layer is provided on at least one surface of the resin film substrate and is in contact with the pressure-sensitive adhesive layer; the pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition containing a rubber-based latex and an aqueous crosslinking agent, The aqueous crosslinking agent includes an aqueous crosslinking agent having at least one functional group selected from an oxazoline group, an isocyanate group, and an epoxy group, The pressure-sensitive adhesive sheet, wherein the undercoat layer contains a water-dispersible polymer having an oxazoline group.

2. The pressure-sensitive adhesive sheet according to claim 1 , wherein the resin film substrate is a polyolefin-based resin film substrate.

3. The pressure-sensitive adhesive sheet according to claim 1 , wherein the water-dispersible polymer having an oxazoline group has a glass transition temperature of 0° C. or lower.

4. 3. The pressure-sensitive adhesive sheet according to claim 1, wherein the content of the aqueous crosslinking agent in the pressure-sensitive adhesive layer is 0.1 parts by weight or more per 100 parts by weight of the rubber latex, based on the non-volatile content.

5. The pressure-sensitive adhesive sheet according to claim 1 , wherein the undercoat layer has a thickness of 0.01 μm or more and 3 μm or less.

6. The pressure-sensitive adhesive sheet according to claim 1 or 2, wherein the rubber-based latex contains natural rubber latex in an amount of 50% by weight or more based on the non-volatile content.

7. The pressure-sensitive adhesive sheet according to claim 1 or 2, which is used for protecting the surface of an adherend.

Citation Information

Patent Citations

  • JP1973041267A

  • Double-sided pressure-sensitive adhesive sheet

    JP2011149002A

  • Aqueous adhesive compositions, adhesive tapes, and wire harnesses

    JP4676945B2